Reagent for forming solid lubricating film, method for producing reagent, method for applying reagent, oil well pipe, and oil well pipe threaded joint
By using a combination of water-soluble polymer and metal soap, combined with lower alcohol and ammonia water, the problem of oil well pipe threads being difficult to dry early in a smoky fire environment is solved, and an environmentally friendly and safe lubrication effect is achieved.
Patent Information
- Application Number
- CN202380060454.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-08-14
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to achieve early drying of oil well pipe threads in an environment where stimulus fireworks are strictly prohibited, and traditional lubricating composites contain harmful heavy metals, which pollute the environment.
Water-soluble or water-dispersible polymers are used as binder resins, and metal soaps are combined as solid lubricants. Early drying of the reagent is achieved through the combination of lower alcohols and ammonia water, and the use of volatile organic solvents is avoided.
Early drying of oil well pipe threads in an environment where stimulus prohibited smoking will prevent the outflow of harmful heavy metals and ensure the safety of operators and the protection of the environment.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to an agent for forming a solid lubricating film that imparts lubricity and corrosion resistance to a metal surface, and a technique using the agent. In addition, the present invention relates to an agent capable of simultaneously achieving lubrication improvement and rust prevention of two objects that are objects composed of metal surfaces and slide, and a solid lubricating film achieved thereby. The present invention relates to a solid lubricating film that is mainly intended for lubrication / rust prevention of oil well pipe threads. In addition, the present invention aims to achieve sufficient lubrication even under the conditions of tightening / loosening in an actual well and to achieve rust prevention at the same time in the use environment. In addition, it is also intended to enable early drying during film formation, including atmospheric drying, air blower drying, hot air blower drying, infrared irradiation, ultraviolet irradiation, and heat treatment.
[0002] At the same time, it is considered that there is a fault in the well and it is overworked. In addition, it is considered that the actual length pins are removed one by one or in units of 2 to 3 and recovered near the well. It should be noted that in an onshore well, for example, the actual length pins are removed one by one. In an offshore well, for example, they are removed in units of 2 to 3. In this case, the oil well pipes are cleaned in parallel. The present invention is also intended to be used as an agent applied to the thread surface for the purpose of protection against rust and the film formed thereby. Background Art
[0003] As a technology close to the present invention, there are technologies described in Patent Documents 1 to 3, for example.
[0004] Patent Document 1 exemplifies a steel pipe threaded joint having an ultraviolet curing resin film as the main body and an acrylic-silicone surface film on the surface. Patent Document 1 exemplifies an epoxy acrylic as the ultraviolet curing resin, and although it is an example that an oily system or a water-based system can be used, it is also clearly stated that the oily system is preferred. That is, the water-based system is not actively adopted. In addition, as the acrylic-silicone surface film, a quick-drying paint-based film and a film in which a metal soap is added to a solid lubricant are exemplified.
[0005] Patent Document 2 is an example of an oil well pipe threaded joint in which a dry solid film is further formed on a viscous liquid or semi-solid lubricating film. An example of forming any of a water-soluble or water-dispersible polymer compound or an organic solvent composition on a dry lubricating film is given. Patent Document 2 gives an example of using a metal soap in a viscous liquid or semi-solid lubricating film. However, Patent Document 2 is an example in which a metal soap is added as a thickening material. It should be noted that in Patent Document 2, the role of the metal soap is not aimed at a solid lubricant.
[0006] Patent Document 3 specifies a lubricating film containing one or both of rosin and calcium fluoride, metal soap, wax, and basic aromatic organic acid metal salt. As optional additives, thermoplastic resins and acrylic resins are exemplified. Examples of using volatile organic compounds as solvents are included.
[0007] In addition, as conventional techniques that are aware of actual tightening in a well, there are, for example, Patent Documents 4 and 5 and Non-Patent Document 1.
[0008] Patent Document 4 describes that a vertical power tong was used, misalignment was assumed, a 7" short pin was used, and an initial setting was conducted at an angle of 6 degrees.
[0009] Patent Document 5 discloses an example of conducting a test evaluation using a vertical power tong and a 9-5 / 8" short pin with a 5-degree offset.
[0010] Non-patent document 1 is a paper evaluating lubrication using a vertical power tong. Furthermore, Non-patent document 1 states that a 5 kN weight is placed at the tip of the short pin opposite to the tightening side, that is, at the upper end of the pin when the pin is tightened upright.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Publication No. 2016-028211
[0014] Patent Document 2: Japanese Patent Application Publication No. 2008-537062
[0015] Patent Document 3: Japanese Patent Re-Publication No. 2009-057754
[0016] Patent Document 4: Japanese Patent Application Publication No. 2002-327874
[0017] Patent Document 5: WO2017 / 110685
[0018] Non-patent literature
[0019] Non-patent literature 1: Jinli et al.: Journal of Petroleum Technology Association, Vol. 61, No. 6 (1996) pp. 527-536.
[0020] Non-Patent Literature 2: Kawamura Chemicals Co., Ltd., Solubility of Metal Soaps, Internet <https: / / www.kawamura-kasei.co.jp / solubility_table.html> Summary of the invention
[0021] Problems to be solved by the invention
[0022] The present invention relates to an agent that simultaneously achieves lubrication improvement and rust prevention of two sliding objects and a solid lubricating film achieved thereby. The present invention aims to provide a solid lubricating film that is mainly intended for lubrication / rust prevention of oil well pipe threads. The present invention aims to simultaneously achieve sufficient lubrication and rust prevention in the use environment even under the tightening / loosening conditions in actual wells. In order to achieve these purposes, the present invention relates to an agent containing a component mainly composed of a metal soap as a solid lubricant in a water-soluble or water-dispersible polymer. In addition, the present invention relates to a solid lubricating film formed using the agent. It should be noted that the water-soluble or water-dispersible polymer is an aqueous polymer.
[0023] The water-based polymer mentioned here refers to a polymer having hydrophilicity by including polar or charged functional groups in the polymer structure, for example, a polymer including a carboxyl group, an amine functional group, a sulfonic acid, etc. in the main chain or the side chain.
[0024] In this regard, there have been the following problems in the past.
[0025] (1) There is no concept regarding a technique for mixing a metal soap in a solvent containing water in an aqueous polymer without using oil, ether, VOC (volatile organic compound), and a group of agents called diluents.
[0026] There has been no prior idea on how to make a metal soap, which is originally considered to be insoluble in water and alcohol, turbid when mixed with an aqueous acrylic acid.
[0027] (2) When an alkaline soap is added to an aqueous polymer, the soap dissolves in water. Therefore, when an alkaline soap is added to an aqueous polymer, water as a solvent tends to become a gelled state with high viscosity. In the past, this has not been studied in oil well pipes.
[0028] (3) When a reagent using an aqueous polymer and a solvent containing water is used, there is a problem in that drying may take a long time.
[0029] Here, among solvents other than water, it is necessary to avoid volatile organic solvents such as xylene, toluene, and benzene. For these, it is necessary to consider that they cannot be used in an environment where fireworks are strictly prohibited, and to consider the safety and health of the workers and the construction of ventilation, etc. Therefore, it is preferred to avoid VOC (volatile organic compounds) and the use of a reagent group called a diluent. The methods exemplified in Patent Documents 1 to 3 are technologies using highly volatile VOCs, and are not intended to be used in an environment where fireworks are strictly prohibited, such as in a well site. Therefore, it is not possible to cope with oil well pipes.
[0030] In addition, for early drying and quick drying, it is also conceivable to use F-based solvents and F-based binder resins that are highly volatile but non-flammable. However, they are essentially unusable. In the U.S. TSCA (Toxic Substances Control Act), after the revision of the rules at the end of April 2021, even if there is past approval, a set of reagents containing PFAS cannot be retroactively used in full. PFAS refers to fluorinated acryloyl groups including PFOS and PFOA. In addition, due to the recent increase in environmental awareness, various countries may also follow. Therefore, for water-based polymers, although it is not possible to achieve quick drying such as drying after coating using methods other than fluorine-based and VOA, it is preferred to have early drying performance within 30 minutes in an environment such as room temperature. The early drying performance is preferably to the extent that it can be dried within 15 minutes as much as possible, and more preferably within 5 minutes. In addition, near oil / gas mining sites, there are extreme conditions such as an environment where fireworks are strictly prohibited. Heat treatment furnaces cannot use electricity either, so it is necessary to imagine an environment where only atmospheric exposure is required. Therefore, it is not possible to perform a process of dispersing the solvent by heat treatment at about 50°C to about 300°C at the well site. The ultraviolet curing resin of Patent Document 1 also means that a device capable of irradiating ultraviolet light is required at the well site. Therefore, in Patent Document 1, a device capable of realizing this technology and equipment such as electrical distribution are required, which cannot be realized.
[0031] If it is a factory that manufactures products with a solid lubricating film formed on the surface, it is not an environment where fireworks are strictly prohibited like a well site. In this case, it is easy to prepare air supply equipment such as large fans, hot air drying equipment, heat treatment, infrared light, ultraviolet light and other drying strengthening equipment. In the case of drying in such a device for the purpose of promoting drying, it is preferably dried within 5 minutes, if possible within 3 minutes, and more preferably within 1 minute. In order to cope with the situation without slowing down the speed of the previous production line, it is necessary to dry within the production cycle of the manufacturing line.
[0032] (4) In order to cope with the recent increase in environmental awareness, there is a problem that a set of reagents containing heavy metals and PFAS needs to be designed so as not to use them. However, it is believed that this will be naturally solved if the above-mentioned problems are solved.
[0033] (5) The present inventors have found that it is important to set upper and lower limits of parameters in order to evaluate the lubrication performance of the solid lubricating film and reagent of the present invention using an evaluation method that conforms to the environment in which the solid lubricating film and reagent are actually used in a well.
[0034] That is, in the conventional laboratory evaluation using a short pin of about 1 m, there is a problem that it cannot be an evaluation method that complies with actual use conditions.
[0035] For example, as in the methods shown in Patent Documents 4 and 5, even if the setting is offset by 5 or 6 degrees and the tightening test is performed using a short pin, the parameter will be wrongly judged as qualified, even to the level of unqualified. As a result, in the methods shown in Patent Documents 4 and 5, there is a problem that the upper and lower limits of the parameters cannot be proved. In fact, the case of setting the offset to 5 or 6 degrees and using a short pin for tightening and loosening tests is considered. In this case, the inclination of the pin thread is mechanically specified in the incomplete threaded portion of the sleeve thread and the tapered portion at the front end of the pin thread. Therefore, even if it is set and inserted at an inclination of 5 or 6 degrees, it is difficult in terms of the structure of the thread. The oil well pipe thread is a tapered thread structure, and its taper angle is roughly at this level. However, it is absolutely impossible for the pin to be tilted at this angle relative to the coupling in terms of structure.
[0036] However, the threads can also be placed without meshing with each other. However, this has nothing to do with the lubrication behavior. Only the initial setting position is different for a moment, and then it is only tightened along the thread cone.
[0037] In addition, the pin thread should be inserted along the tapered shape of the thread. Moreover, there should be an inclination due to the looseness of the threads during insertion. When the pin thread is inserted into the sleeve thread, it is structurally difficult to always set an inclination of about 5 degrees. It is estimated that due to the looseness of the threads, only an inclination of 1 to 2 degrees can be set. In fact, even starting from this state, when the threads are engaged with each other, the pin thread immediately stands up straight. Therefore, it is estimated that when the threads are almost not engaged with each other, when the inclination is about 5 degrees, the damage to the solid lubricating film is small, and it cannot be a simulation of actual well conditions.
[0038] In addition, the method of making the pin thread bear a weight of 500 kN to bear the load of an actual pin as in Non-Patent Document 1 also has problems as an evaluation method. As described in detail in the following invention, the initial setting position is important for reproducing the simulation of the loosening of the pin thread in the actual well. In Non-Patent Document 1, as Figure 5 As confirmed by the invention, if the pin is tightened manually to a position where it can be tightened in about half a turn, the weight becomes a counterweight and is tightened straight in an ideal pin state. Therefore, in an actual well, it is impossible to simulate a strict condition in which the pin thread is tightened and loosened while having looseness, based on the fact that the long pin is slightly bent in the elastic region. The strict condition is, for example, the same condition as in an actual well.
[0039] Here, the inventors have found that the initial setting position of the pin thread is intentionally set as follows, and the result that matches the conditions of the actual well or simulated well cannot be estimated unless tightening and loosening are performed. The setting is to set the pin thread to a position where it is exposed from the sleeve thread and further to make the pin end bear a weight equivalent to one to three actual-size pins.
[0040] Here, it should be noted that the lubrication evaluation of solid lubricating films is different from the lubrication of conventional composite materials using viscous liquids, and there is a tendency for the evaluation results using simple short pins to deviate from the results of actual wells. Specifically, the evaluation results are slightly loose. That is, even if the evaluation is qualified in the test using short pins, it does not mean that it is qualified in the actual well. Therefore, in the case of solid lubricating films, as long as the evaluation of lubrication is not set to be strict, the upper and lower limits of the parameters will not be a proof of the lubrication that can be tolerated in the well.
[0041] The present invention has been made with an eye on the above-mentioned problems. Furthermore, an object of the present invention is to provide a solid lubricating film which is environmentally friendly even when a water-soluble or water-dispersible polymer is used as a binder resin and a water solvent mainly composed of a metal soap is used as a solid lubricant, and which has lubricating properties that can withstand use in actual wells.
[0042] Methods used to solve problems
[0043] Regarding the lubrication of oil well pipe threads, there is a tendency that the reagents used as reagents and the components of the lubricating film are limited due to the recent increase in environmental awareness.
[0044] In the past, the lubrication of oil well pipe threads was composed of, for example, a combination of a lubricating compound containing harmful heavy metals and a surface treatment on the sleeve thread side. It should be noted that the surface treatment, for example, includes a phosphoric acid Mn base or an electroplating layer. However, the commonly used API-mod compound, i.e., a wet lubricant, has become difficult to use in areas and regions with high environmental awareness. Specifically, the API-mod compound contains harmful heavy metals such as Pb and Zn as main components. Therefore, when tightening, the harmful heavy metals are washed away or overflow to the outside, which may result in pollution of the ocean.
[0045] In the present invention, a solid lubricating film is used instead of these lubricating composites. In addition, in the present invention, a water-soluble or water-dispersible polymer is used as a binder resin of the solid lubricating film. Therefore, in the present invention, the problem of outflow of harmful heavy metals is avoided.
[0046] Originally, the solvent in the solid lubricating film forming reagent that is the subject of this application is water, which itself has no problem in terms of environmental resistance. The binder resin and solid lubricant only need to meet the international regulations and rules of the reagent system. Therefore, in order to achieve HSE at the same time and also ensure the safety and hygiene of the operator, using a solid lubricating film instead of the conventional lubrication of the oil well pipe thread is also effective in solving the HSE problem. HSE is the abbreviation of health, safety and environment.
[0047] Furthermore, the wet compound used in the conventional lubrication method is often different from the compound used for lubrication and the compound used for storage.
[0048] In the technology of replacing the lubrication method based on wet compound with solid lubricating film, dry film should be used for rust prevention during storage. In addition, for rust protection of pin threads, it is not preferred to use the conventional wet compound except in emergency.
[0049] That is, it is considered that the solid lubricating film is preferably designed to be a film having rust prevention properties during storage while being a lubricating film.
[0050] In addition, it should be noted that in the technologies used in the past, lubricating compounds and corrosion-resistant compounds are all viscous liquid compounds. Therefore, these compounds function in a wet state. In other words, wet compounds do not need to consider drying time.
[0051] On the other hand, the solid lubricating film is a dry film and functions in a dry state. Therefore, when forming the solid lubricating film, it is necessary to design the agent including the operation of evaporating the solvent from the applied agent to form a film and the time required for the operation.
[0052] Here, there has been a technique for designing a dry soft polymer resin film using a reagent based on a water-soluble or water-dispersible polymer, particularly a technique used for surface lubrication of oil well pipe threaded joints. In addition, there has also been a technique for providing high lubrication using a metal soap as a main component as a solid lubricant.
[0053] However, it is not known that a metal soap is dispersed as a main component of a solid lubricant in a dry soft polymer resin film formed using a simple water-soluble or water-dispersible polymer, which corresponds to a combination of these. It should be noted that the polymer resin film is a base component.
[0054] In the past, it was considered difficult to add a water-repellent and water-insoluble metal soap to a water-based solvent alone without mixing oil or diluent. It is not impossible to use a metal soap as a solid lubricant in a water-based solvent alone, but it is difficult to achieve under the conditions of the present invention. Metal soap is water-repellent and will float on the surface even if it is simply mixed with water, rather than being dispersed and dissolved.
[0055] The present invention relates to a design in which a dry soft polymer resin film is formed using a water-soluble or water-dispersible polymer and a solid lubricant is dispersed in the film. Furthermore, in the present invention, a metal soap is positioned as a main component of the solid lubricant.
[0056] Metal soap itself has water repellency and is insoluble in water. At the same time, metal soap itself is also insoluble in the alcohol group. Metal soap itself slightly dissolves VOC (volatile organic compounds) and a reagent group called diluents. However, most of these reagents are harmful to health and are reagents widely called diluents. Moreover, these reagents are classified into a VOC group of toluene, xylene, benzene, mineral spirits, an ether group, and an oil widely called mineral oil. This information is widely known public information.
[0057] Therefore, it was previously considered difficult to directly mix the metal soap itself into the water-based polymer. Therefore, in the past, the metal soap was dissolved in the VOC listed above and then turbid in a solvent mainly composed of water. Methods using diluents, etc. are described in, for example, Patent Documents 1 to 3. However, as described later, it is highly likely that the metal soap cannot be used in places where fireworks are strictly prohibited, such as in oil / gas mining environments, for the sake of operator safety and the environment.
[0058] The present invention also envisions the case where alkaline soap is also dispersed. Here, alkaline soap is a soap of either or both of Na salt and K salt of fatty acid. Hereinafter, alkaline soap is also referred to as soap. In the present invention, it is also envisioned to use a trace amount of alkaline soap to assist and enhance lubrication. Although repeated, in the present invention, the solid lubricant is dispersed in the film in a state where the water-soluble or water-dispersible polymer is formed into a dry soft polymer-based resin film.
[0059] Soap is different from metal soap, which is soluble in water. Therefore, for the reagent and solid lubricating film considered by the present invention, it is difficult to use alkaline soap. In addition, there are almost no application examples in the past. If a water-based polymer design is added with a certain amount of alkaline soap, the entire liquid becomes gelled and solidified. As a result, the fluidity unique to the water system becomes higher. That is, the feature of easy coating disappears, and there is a tendency to be difficult to dry early.
[0060] On the other hand, in society, soap-based lubricants used in a water-wet state are commercially available in large quantities even for industrial use. However, this is a technology that effectively utilizes lubrication in a hard gel state without drying. Therefore, this is a different system from the technology of the present invention.
[0061] As mentioned above, in the past, water-based polymers refer to polymers that make the solvent water. When filming, it is necessary to dry and remove the water component. Water-based polymers are water-soluble or water-dispersible polymers. Since the solvent of water-based polymers is water, the object to be coated is heated. On the contrary, there is also a method of coating after heating the object position to be coated. In either case, if there is no process to promote the volatilization and evaporation of water, the coated product will be retained in the production plant until drying. This will significantly reduce manufacturing efficiency. That is, when drying by placing in the atmosphere, a large amount of drying time is required, and a drying place needs to be ensured. Therefore, as long as the water-based polymer does not carry out research on early drying, production efficiency will be reduced, and as a result, manufacturing cost becomes high. That is, for early drying, when carrying out device processing, a drying device and a heat treatment furnace are required. However, this causes the installation cost and running cost to increase.
[0062] On the other hand, in order to dry the water-based polymer early, it is also known that a volatile organic solvent is added to effectively utilize the volatilization heat to form a film. Patent Document 1 states that in order to form a dry film in a short time at a relatively low temperature, an oily film can be selected as the surface film of acrylic-silicone, and a room temperature curing film is particularly preferred. That is, Patent Document 1 is an example of achieving early drying by effectively utilizing the volatilization of an oily solvent without selecting a water-based system.
[0063] Patent Document 2 exemplifies a system of water alone, a system of water + volatile organic solvent, and a system using ultraviolet curing resin. Of these three points, the latter two can achieve early drying. However, in the first polymer of the water-only system, it is necessary to use some method to evaporate water. However, Patent Document 2 does not explicitly describe this method.
[0064] Patent document 3 discloses a method of using a volatile solvent and a solvent with a flash point of 30°C or more to speed up the drying time. However, when the flash point is about 30°C, in hot areas such as desert areas in midsummer, if there are dangerous factors such as sparks, there is a high concern about fire at the well site. Moreover, even if processing is performed in a workshop slightly away from the well, the concern about fire cannot be denied. In this way, if materials with a low flash point are not used in a fully managed environment, there is a problem of increasing the concern about accidents such as fire. That is, in the past, there was a problem about how to dry safely and early. Materials with a low flash point refer to materials that are easily ignited.
[0065] On the other hand, in the present invention, the solid lubricating film is composed mainly of a water-soluble or water-dispersible polymer.
[0066] In order to speed up the drying of aqueous solvents, a method of using a reagent group called a VOC (volatile organic compound) and a diluent to effectively utilize their volatility is considered. However, there are also rules for suppressing the emission of VOC, and in order not to place the operator in a bad environment, the inventor judges that no matter how high the volatility of organic solvents such as toluene, xylene, benzene, etc. is, it is effective for early drying, but it should also be avoided. Even if an exhaust device is prepared, it is likely to become a huge equipment investment. In addition, when forming a solid lubricating film, it is difficult to use a volatile organic solvent that is harmful to the body in the reagent. Therefore, the inventor judges that in order to achieve early drying, it is impossible to use a reagent group called a diluent that is harmful to health and has too high volatility.
[0067] In addition, the fluorine-based solvents that originally had quick drying properties and the fluorine-based resins that could be dissolved in them to form the binder resin component of the paint are changing in the direction of not being used recently. Fluorine-based solvents are freon substitutes, etc.
[0068] In the past, fluorine compounds have been a typical surface treatment due to their quick drying properties, excellent lubrication and corrosion resistance. However, due to the recent strengthening of regulations, fluorine compounds have become unusable. In the US TSCA (Toxic Substances Control Act) and the European chemical reagent regulation REACH, F-alkyl compounds (F-(CF 2 ) n -) So far, only PFOS (perfluorooctane sulfonic acid) and PFOA (perfluorooctanoic acid) are restricted (chemical species containing fluorine compounds with 8 Cs). There are no special problems with fluorine-based compounds with fewer Cs and they can be used. However, in the revision of the US TSCA in April 2021, the importation and production of PFAS (organic fluorine compounds: perfluoroalkyl compounds and polyfluoroalkyl compounds) reagents into the United States for use and production were almost completely banned in the past. As a result, it has become a situation where binder resins containing fluorine compounds (PFAS) cannot be used. That is, the only reagents and products that can be used in a fluorine-containing manner are Teflon (registered trademark) (PTFE: polytetrafluoroethylene) and PFPE (perfluoropolyether) that are exempted from the application of TSCA. Moreover, the international trend of designing solid lubricating films in the direction of not using fluorine can no longer be ignored.
[0069] Based on the above circumstances, the present invention considers preparing a reagent having a composition in which water is used as a solvent and a binder resin is also soluble in water in order to cope with the environment, forming the reagent with an appropriate solid lubricant and other additives, and using the reagent to prepare a solid lubricating film.
[0070] However, water as a solvent has problems such as being difficult to volatilize and taking time to evaporate. In addition, drying requires huge equipment investment such as a heat treatment furnace.
[0071] In addition, when a solid lubricating film is applied to the threaded portion of an oil well pipe thread, the oil well pipe is produced and transported at a location far away from the oil / gas well. Therefore, at this production base, when a solid lubricating film based on a water-soluble or water-dispersible polymer is produced, it may seem that all problems related to quick drying and early drying can be dealt with. That is, since water-based polymers are difficult to dry, it is possible to adopt the following countermeasures: making equipment that takes time to dry, or working on production that promotes drying using heat treatment equipment, etc. At this time, without using a heat treatment device, the addition of a volatile organic solvent to promote drying is also considered. In addition, there are many situations where this can be achieved by ensuring exhaust equipment and adopting non-ignition countermeasures.
[0072] However, when a solid lubricating film-forming agent, a solid lubricating film formed using the agent is used in an oil well pipe threaded joint, and the oil well pipe threaded joint is used in a well, there is a problem that the solid lubricating film is not necessarily produced or formed only at a production base far from the well.
[0073] In the case of failure of the lubricating film formed on the oil well pipe, it is also necessary to assume that the reagent for forming the solid lubricating film is used at the well site. At the well site, it is an environment where pyrotechnics are strictly prohibited, and there are also situations where the scaffolding is not strong. In addition, when applying a water-soluble or water-dispersible polymer at the well site, there is a requirement for rapid drying.
[0074] The reason is that when a failure occurs in a well, there is a situation where the pipe thread is pulled up from the well to the vicinity while loosening in units of one to three threads. In this case, it is necessary to align the pulled pins (oil well pipes) horizontally, clean the pin surfaces with water, steam, etc., and then apply a substance similar to a storage coating for rust prevention. In response to this, the conventional method of the oil well pipe thread method has established that it is not to apply a wet lubricating compound containing Pb and Zn such as API-mod compound, but to apply a compound called a wet storage compound to deal with it.
[0075] In contrast, in the case of a solid lubricating film, in order to complete it only with the solid lubricating film technology, it is necessary to form a solid film base that can be dried early at the well site, unlike the wet compound. However, fireworks are strictly prohibited at the well site. It is dangerous to use an organic solvent with a low flash point and good volatility that promotes early drying, so it cannot be achieved.
[0076] For example, according to the records in Patent Documents 1 to 3, in order to achieve early membrane formation, organic solvents with low or very low flash points and high volatility were used. Moreover, it is presumed that the reagents were designed based on the premise that oil well pipes were produced and transported at locations far from oil / gas wells. It is extremely dangerous to use reagents based on reagents with low flash points near oil / gas wells where fireworks are strictly prohibited.
[0077] The present invention provides a reagent that uses no highly volatile organic solvent as much as possible.
[0078] In addition, the inventors did not intend to evaluate the corrosion resistance and lubrication issues that are often encountered in daily life through simple laboratory experiments and simulations. The inventors studied previous laboratory tests and obtained the following insight: it is necessary to set the system to be able to cope with even the most stringent conditions that can be imagined.
[0079] In the present invention, regarding corrosion resistance, it is assumed that the solid lubricating film is damaged, not corrosion resistance in a state where the film is simply formed. Under the most stringent conditions that can be assumed, it is assumed that the surface of the solid lubricating film of the oil well pipe thread needs to be able to maintain corrosion resistance after tightening and loosening using a protective device. That is, in the present invention, it is assumed that it is necessary to maintain corrosion resistance even in a state where the solid lubricating film is damaged due to contact with the protective device.
[0080] At the same time, in the present invention, for lubricity, it is assumed that good lubricity needs to be ensured under sliding conditions with high loads. Regarding the solid lubricating film, if the actual well is taken into consideration, it is necessary to assume that the solid lubricating film is inevitably ground to some extent during tightening and loosening. The inventors of the present invention have obtained the following insight: the ground fragments become the source of burn failures under the following circumstances. This situation refers to the situation where the gap between the sleeve thread and the pin thread is blocked, the situation where a high load and an eccentric load are applied to the butt joint, the situation where a part of the film is removed without leaving any part, etc. In addition, the following insight has been obtained: for lubrication performance simulating the conditions of an actual well or close to a well, if the upper and lower limits of the composition of the solid lubricating film are not set, then its regulation is meaningless in an actual well.
[0081] Here, as a test that has been frequently used in the past, there is a tightening test in a laboratory using only a short pin of about 1 m. In this tightening test, regarding the lubrication of the solid lubricating film that is the object of the present invention, the case where the NG judgment is made is also NG in the actual well. However, in this previous test, even if the evaluation in the test using the short pin of about 1 m is judged as OK, there is no guarantee that the judgment is also OK in the actual well. However, in the prescribed range of lubrication performance of the solid lubricating film in the past patent documents, the prescribed range of the solid lubricating film is rarely selected in consideration of this point.
[0082] It should be noted that, in the case of the viscous liquid lubricating compound commonly used in the lubrication of oil well pipe threads in the past, there is not much difference between the tightening and loosening evaluation using a short pin in the laboratory and the actual situation in the well. In addition, based on the evaluation in the laboratory, the judgment in the actual well also tends to be linked. This is because, due to the viscous liquid lubricating compound, it is effective to assume that the compound moves in a linked manner during tightening and loosening.
[0083] On the other hand, in the case of a solid lubricating film, the fragments that are inevitably ground do not necessarily move in conjunction with tightening and loosening. Therefore, in an actual well where the generation of fragments increases anyway, the fragments are easily clogged. In addition, when peeling occurs significantly, burns occur in the portion where the solid lubricating film becomes thinner or disappears. Based on such insights, the inventors have obtained insights that it is necessary to perform evaluation based on this in the evaluation of solid lubricating films.
[0084] This viewpoint will be described in more detail.
[0085] In actual wells, the situation where the actual length of the pin thread is tightened to the sleeve thread is not implemented under the ideal state as described in the textbook. Under the ideal state, it is believed that the actual size pin is set upright and embedded relative to the sleeve thread, and it becomes an image of being tightened straight. However, this is not the case in reality. The structure of the oil well pipe thread has an incomplete thread portion when the pin thread enters the sleeve thread in the form of insertion. Moreover, at the time of initial setting, the pin is often set slightly tilted by the amount of looseness (clearance, margin) of this part. Moreover, at the beginning of the tightening of the thread, the pin thread rotates in contact with the amount of clearance. Therefore, before the threads are engaged with each other, the weight of the pin as a large load is superimposed on the offset load for the offset movement of the pin for the solid lubricating film. Therefore, in any case, the concern that the solid lubricating film is abnormally ground or stripped off without leaving any residue becomes high. On the other hand, the wet lubricating compound is a viscous liquid lubricant, so it moves in conjunction with tightening / loosening. Therefore, in the lubrication composite, the evaluation method of lubrication in the laboratory using a short pin is roughly the same as the results in the actual well, which is the preferred control.
[0086] Put it in Figure 2 , Figure 3 Specifically shown in FIG.
[0087] Figure 2 , Figure 3 The example shown in the example is an example of a tightening and loosening test condition where the screw is rotated at 15 to 25 rpm before the torque rises and at 2.5 to 1.5 rpm after the torque rises. This is the result of a test under strict conditions, i.e., a high rotation speed, which exceeds the conditions specified in the operating instructions of the thread, i.e., the tightening instructions in the Technical package. Figure 2 , Figure 3 The example shown in the figure is the use of JFELION for cementing materials and 9-5 / 8” 53.5# Q125 raw materials with strength grade TM An example of evaluating a solid lubricant coating on a thread.
[0088] Figure 2 This is a torque rotation diagram based on the previous laboratory evaluation method using a short pin of about 1m and tightening with a vertical power tong. Since the pin is short, it is not difficult to operate and the pin can be set straight. Therefore, by manual tightening, the pin can be set to a state where the pin thread is almost not exposed ( Figure 2 (b)). In the torque rotation diagram in this case, the torque starts to rise from the start of tightening, exceeds the bending point of the shoulder torque, and tightens. That is, in this case, it is a very common diagram ( Figure 2 (a)). Here, the torque rises immediately because the pin thread and the sleeve thread are fully engaged in the initial setting stage and tightening is performed from the preset position.
[0089] on the other hand, Figure 3 This is the torque rotation diagram when using a Range-3, which is a real-size pin of more than 40 feet (more than 12 meters). Figure 3 is the result of the test in the simulated well. Here, the unit (size) of the horizontal axis is Figure 2 Different. It should be noted that the simulated well is not an actual well that produces oil / gas, but an experimental well in which a hole is opened in a simulated manner by inserting more than three actual-sized pins into the underground direction, that is, downward. At the same time, the simulated well refers to a device group or experimental facility that has a stand that can be set up with about 2 to about 3 connected pins suspended from its ceiling and can perform tightening and loosening tests. This example is a tendency under the same setting as the setting in the actual well, but it is different from the short pin. Figure 2In this case, the stable torque did not rise until about 6.3 revolutions, and a spike-shaped torque was observed to rise irregularly from time to time during the rotation. The inventors have found that this phenomenon is directly related to the damage of the solid lubricating film, and it is important to evaluate the solid lubricating film based on this phenomenon.
[0090] Should Figure 3 The torque example occurs when setting Range-3, that is, a pin of more than 40 feet (more than 12m) and tightening it. In this case, since it is an actual size pin of more than 12m, the pin cannot be set completely straight, and the pin is almost always inserted at an angle. It should be noted that this is the same condition as the actual well. Therefore, even if the pin is set by manual tightening, the pin thread and the sleeve thread will partially touch too strongly. Therefore, when the pin thread teeth are more than 5 teeth, about half of the total thread teeth cannot move forward further when exposed from the sleeve during manual tightening. From this state, tightening with pliers is started. Moreover, the threads are almost always not fully engaged with each other, and a part of them accidentally touches strongly, becoming a state that cannot move forward further. Therefore, before the threads of the actual size pin are fully engaged with each other, the sleeve thread and the pin thread touch each other under the load offset state. That is, it means that damage is caused to each other. On this basis, the following understanding was obtained: if the solid lubricating film is not evaluated, then as described above, NG in the evaluation using a short pin alone is NG in the actual well, but OK in the evaluation using a short pin does not necessarily mean OK in the actual well. Therefore, the following understanding was obtained: in the upper and lower limit regulations of components, conditions and other parameters in the previous invention, the regulations evaluated based on OK in the evaluation of the short pin are not necessarily a good range in the actual well.
[0091] Here, the methods of Patent Documents 4 and 5 are examples of test evaluation using a short pin, which is not necessarily a good range.
[0092] In addition, in non-patent document 1, when the pin is fastened upright, a 5kN weight is placed on the upper end of the pin to evaluate lubrication. Here, in non-patent document 1, when judging based on the torque rotation diagram of the 7" 29# pin, it is considered that the weight of a pin of actual length, that is, about 40 feet (about 12m), is applied. However, in non-patent document 1, when judging based on the torque rotation diagram, that is, the weight of the document, Figure 5 When making judgments, it is considered that Figure 2 The tightening behavior is tested as a prerequisite, not Figure 3 That is, in Non-Patent Document 1, it is considered that the initial setting position is tightened by manual tightening to a level where the pin thread is not exposed, and the tightening test is performed from a state where the pin thread and the sleeve thread are fully engaged. Therefore, it is not necessarily possible to find a good range.
[0093] The following describes the problems extracted from the above description regarding the present invention.
[0094] The present invention is based on the premise that no volatile organic solvents such as oils or diluents are used. Under this premise, the present invention considers dispersing a solid lubricant component mainly composed of a metal soap in a binder resin containing a water-soluble or water-dispersible polymer to prepare a reagent. Furthermore, it is considered to use this reagent to prepare a lubricating film having corrosion resistance including a solid lubricating film.
[0095] With regard to such a configuration, we have found that there are the following problems. Therefore, we have found that further research is necessary.
[0096] (First Topic)
[0097] This is a problem when mixing metal soap with water-based polymers. That is, it is necessary to study how to make the water-insoluble metal soap cloudy without using oil, volatile organic compounds, and a reagent group called a diluent.
[0098] (Second Topic)
[0099] If an alkaline soap is added to an aqueous polymer, the solvent tends to become a highly viscous gelled state because the alkaline soap is soluble in water. Therefore, if an alkaline soap is added to an aqueous polymer, even if the alkaline soap has lubricating properties, it may take time to form a film. At the same time, in order to form a solid lubricating film in a dry state, it is necessary to specify an appropriate amount of alkaline soap.
[0100] (Third Topic)
[0101] Since water-based polymers are used and water is used as a solvent, there is a high concern that drying after coating takes time. Therefore, some aspects that require research in order to achieve early drying can be listed as topics. In short, it is preferred to dry early wherever coating is applied.
[0102] In extreme situations such as an environment where fireworks are strictly prohibited, neither the heat treatment furnace nor electricity can be used, and there are also environments where only the atmosphere can be left. However, the present invention envisions that the solid lubricating film and reagent can be used not only at the manufacturing site of oil well pipe products but also at the well site. Therefore, in order to improve the quick-drying performance, it is necessary to avoid the use of diluent VOCs at the well site where fireworks are strictly prohibited. At the same time, it is necessary to consider the safety and health of the operators and the construction of ventilation, etc. Therefore, it is necessary to design the solid lubricating film and reagent on the premise that the use of diluent VOCs should be avoided.
[0103] (Fourth Topic)
[0104] In order to cope with the recent increase in environmental awareness, it is necessary to use a set of reagents that do not contain heavy metals and PFAS (fluorinated acryloyl groups including PFOS and PFOA). It should be noted that PFAS is a fluorinated acryloyl group including PFOS and PFOA.
[0105] (Fifth Topic)
[0106] It is important to evaluate the lubrication and the like of the solid lubricating film and reagent of the present invention and set the upper and lower limits of the parameters by an evaluation method that conforms to the environment in which the solid lubricating film and reagent are actually used. However, the evaluation method in the past using a short pin of about 1 m was not based on the actual use conditions.
[0107] Hereinafter, means for solving each problem in the present invention will be described.
[0108] The present invention is a reagent in which a water-soluble or water-dispersible polymer, i.e., an aqueous polymer, is used as a binder resin, a solid lubricant is mainly composed of a metal soap, and a solvent is mainly composed of water. Also, the present invention is a solid lubricating film formed by the reagent.
[0109] Metal soap functions as a solid lubricant with water repellency. Water repellency means being insoluble in water. In the reagent, under the premise that the metal soap can be well mixed, it is considered that good lubricity, corrosion resistance, early drying and other properties are established within the range specified by the present invention. In order to solve the above problems, the present invention uses the following solution means to define and constitute the invention.
[0110] A method for solving the first problem is a technique for well mixing the metal soap in water as a solvent.
[0111] Generally, it is explained that metal soap is insoluble in water and alcohol, and can be dissolved in volatile organic solvents, ethers and oils of the diluent type. For example, it is clearly stated in Non-Patent Document 2 that metal soap is insoluble in ethanol, methanol and butanol. That is, if water is selected as the solvent, and VOC that is easily volatile at room temperature is used, and the operator needs a special mask or ventilation equipment, the metal soap will dissolve. However, in the past, it was believed that there was no solution to dissolve the metal soap in water as long as such substances were not added.
[0112] In addition, if the lubrication of oil well pipe threads is taken into consideration and the reagent is applied at the well site, there is a difficulty in using thinner-type solvents in the well site environment where pyrotechnics are strictly prohibited. Thinner-type solvents can be said to be solvent substances that do not remain in the formed film and cannot be used.
[0113] The present inventors have studied and conducted experiments on mixing a water-insoluble metal soap with water, which is a solvent for a water-soluble or water-dispersible polymer, i.e., a water-based polymer. In this experiment, the metal soap is insoluble in neither water nor ethanol, but when actually trying to dissolve it, when comparing water and a group of lower alcohols represented by ethanol, experimental observations revealed that the dispersion of the metal soap was different.
[0114] Specifically, it was found that: in the group of lower alcohols represented by ethanol, the metal soap has a tendency to be difficult to agglomerate and easy to be micronized, and the metal soap can maintain the state of microparticles. After the metal soap and alcohol are mixed, strong stirring or ultrasonic vibration can be applied. On the other hand, in water, the metal soap associates to become larger and agglomerates, and the metal soap cannot be in a uniformly dispersed state.
[0115] This yielded the following findings: by temporarily dissolving the metal soap in a lower alcohol group such as ethanol, the metal soap can be dispersed but insoluble, and by subsequently mixing it in an aqueous polymer, a nearly homogeneous reagent can be obtained.
[0116] When the reagent of the present invention is left to stand, the metal soap separates over time. However, when the reagent of the present invention is used, i.e. applied, the container containing the reagent of the present invention is shaken to make it turbid again before applying, and if the water of the solvent is scattered, i.e. evaporated or volatilized after application, it is confirmed that a homogeneous solid lubricating film is formed.
[0117] Note that, when the metal soap is directly dissolved in water, the metal soap tends to clump together, and therefore, when a solid lubricating film is formed, there is a high risk of forming an inhomogeneous film.
[0118] The reasons for the above are not very clear.
[0119] Qualitatively, water is only a polar solvent. On the other hand, the lower alcohol group represented by ethanol has a tendency to be slightly soluble in oil while being soluble in water. Metal soaps are insoluble in water, but are generally described as being insoluble in alcohol. However, on the other hand, metal soaps can be dissolved in oils, VOCs known as diluents. Therefore, the horizontal view of insolubility may be a difference at the molecular level, and it is presumed to be effective for the difference in the phenomenon described above.
[0120] On the other hand, the lower alcohol group represented by ethanol also has high volatility and belongs to the category of VOC. Therefore, in an environment where fireworks are strictly prohibited, there is a concern that it may easily catch fire. Therefore, regarding the lower alcohol used to dissolve the above-mentioned metal soap, it is necessary to set an upper limit on the amount that can be used and the concentration in the reagent. From this point of view, the present invention stipulates an upper limit for the lower alcohol.
[0121] In order to use it as a solid lubricant, the more metal soap is dissolved, the better. However, the upper limit of the amount of metal soap dissolved is determined by the solubility limit of alcohol, volatility, and flash point. In addition, the lower limit of the metal soap is determined by the minimum amount that can achieve lubrication.
[0122] The second issue is how to mix a small amount of alkaline soap as a support for lubrication.
[0123] That is, how to mix a trace amount of alkaline soap into a system in which the binder resin is a water-based polymer, the main component of the solid lubricant is a metal soap, and the solvent is water without adding VOCs such as a diluent.
[0124] Since alkaline soap is soluble in water, it can be mixed. However, if alkaline soap is excessively dissolved, water as a solvent tends to become a gelled state with high viscosity. Therefore, when applying the reagent, the reagent is difficult to dry, and it takes time to dry as a solid film. In addition, when drying, it becomes a semi-solid film with high viscosity. Moreover, for semi-solid to viscoelastic films, stickiness remains on the surface, so dust and sand are easily attached. If dust and the like are attached, it is difficult to remove. Such a situation becomes a resistance when tightening and loosening, and it may not be possible to achieve the necessary lubrication.
[0125] Based on the above, in order to add an amount of alkaline soap that can support the effect of solid lubrication without changing the viscosity of water as a solvent, it is necessary to add alkaline soap in a trace amount and set an upper limit. From this point of view, the present invention specifies the amount of alkaline soap added.
[0126] The third problem is that since the aqueous polymer uses water as a solvent, it may take time to dry when the reagent is applied.
[0127] In the present invention, a large amount of VOC is added and the water is evaporated by using its volatility, and an environment where fireworks are strictly prohibited is not assumed. If the health and safety of the workers are taken into consideration, toluene, xylene, and benzene-based VOCs, which are called diluents, cannot be used. In addition, including an environment where an electric heater cannot be used, or a situation where the film is dried only by placing it outdoors in the environment of the land, it is necessary to dry the film safely.
[0128] In the present invention, the lower alcohols listed in the first topic, i.e., ethanol, methanol, isopropanol, n-propanol, industrial ethanol and the like, are used to dissolve the metal soap. At this time, as described above, in order to be used even in an environment where fireworks are strictly prohibited, the alcohols can be formulated within a range that does not cause any problem according to volatility and flash point.
[0129] In order to use in an environment where fireworks are strictly prohibited, the flash point of the reagent is set to be 60° C. or higher, preferably 150° C. or higher, and more preferably 250° C. or higher. Furthermore, under these conditions, an excess of lower alcohol groups is added to dissolve the metal soap, and their volatility is effectively utilized.
[0130] However, setting the flash point higher means that the amount of alcohol added and the content are reduced. However, the lower alcohol group is preferably contained at least 0.5%.
[0131] At the same time, ammonia can also be added and its volatility can be effectively utilized.
[0132] Aqueous ammonia is sometimes used to adjust the pH of a coating. When used for pH adjustment, in order to distribute to the upper limit of the specified pH of the reagent, i.e., the high pH side, additional aqueous ammonia is added for preparation. In addition, when the pH adjustment is not specified, aqueous ammonia (28-30%) or the like may be added with an upper limit of 1% in volume / volume % relative to the water in the solvent to achieve promotion of volatility. In the present invention, the conditions for the simultaneous use of ethanol and ammonia are clarified through experiments, and the optimal range is clarified. Regarding aqueous ammonia, as commercially available aqueous ammonia, there is also aqueous ammonia diluted to a level of 10% or 5%. However, in the present invention, the conversion discussion is based on concentrated aqueous ammonia (28-30%).
[0133] Meanwhile, in the present invention, a small particle size is selected as the particle size of the metal soap. Furthermore, by dispersing the metal soap in the reagent in a manner that prevents the metal soap from being associated, the contact surface area of the metal soap is increased, thereby achieving early drying.
[0134] Regarding the size of the metal soap, the drying of the applied reagent is promoted by using a metal soap having an average particle size of 10 μm or less, preferably 5 μm or less, and more preferably 1 μm or less. In addition, in order to disperse and mix them into the reagent, as clearly stated in the response to the first problem, the reagent is prepared by dissolving them in a lower alcohol represented by ethanol.
[0135] In addition, it is also important to adjust the viscosity of the reagent, to lower the viscosity so that the reagent can be applied thinly, or to make it difficult to apply thickly.
[0136] If the reagent is applied to the metal surface of the cylinder while the cylinder is rotating, the excess reagent will inevitably fall from the 6 o'clock position, which is the lowest position. In addition, when the cylinder is not rotating, although there is a tendency to apply a slightly thick coating at the 6 o'clock position, the excess reagent will inevitably fall from the 6 o'clock position. Even when the reagent is applied to a plate-like object, as long as it is in a state of being tilted and erected, the excess reagent will fall due to its own weight. This can form a state that is easy to dry early.
[0137] Therefore, in order to achieve early drying, even when the metal surface coated with the reagent is placed indoors or outdoors in the atmospheric environment, early drying can be achieved under the following conditions. The conditions refer to a combination of selecting the above-mentioned alcohol and ammonia for effective use, the particle size of the metal soap, considerations of preventing the metal soap from associating and agglomerating, and adjusting the viscosity of the reagent to prevent thick coating.
[0138] The fourth challenge is to design a method that does not use a set of reagents that include heavy metals and PFAS. PFAS refers to fluorinated acryloyl groups including PFOS and PFOA.
[0139] On the other hand, the present invention is not constituted by using harmful substances in aqueous polymers, and therefore, if the means for solving the above-mentioned problems 1 to 3 are implemented, these problems can be solved naturally.
[0140] The fifth issue is that it is necessary to evaluate the properties of the lubricating and anticorrosive films by using appropriate evaluation methods, thereby defining upper and lower limits for each material.
[0141] First, regarding the corrosion resistance and corrosion resistance of the present invention, the most stringent conditions are considered, and lubrication of oil well pipe threaded joints is assumed. In the evaluation of corrosion resistance in a state where a film is simply applied to a plate, or lubrication behavior using a short pin, even if NG can be screened, it cannot be asserted as qualified.
[0142] In the present invention, regarding the corrosion resistance, the corrosion resistance of the film is not assumed only when the agent is applied to form a film. That is, regarding the corrosion resistance, it is necessary to assume that the film is partially in contact with the protector when fastened by the protector, thereby causing damage to the film.
[0143] In addition, regarding lubrication, in an actual well, the actual length pin of Range-3, that is, a pin of about 40 feet (about 12m), is erected, hoisted and tightened with a mast crane, etc. In the worst case, there is a situation where the weight of the actual length pin is entirely applied to the threaded side of the sleeve. It should be noted that this is equivalent to a 9-5 / 8" 53.8#, which is about 1 ton. Due to its large load, it is necessary to also consider the situation where the solid lubricating film is significantly damaged.
[0144] The initial setting position of the actual length pin is also different from that of the short pin. It is assumed that the pin thread teeth are almost completely hidden in the sleeve thread and cannot be set. In other words, it is necessary to evaluate the lubrication by assuming that the pin can only be tightened to the position where the thread teeth cannot be further advanced, that is, the position where the thread teeth are exposed. For example, in an actual well, it is only possible to set the pin thread teeth at the position equivalent to Figure 3 A pin thread is provided at the position of symbol 1a (10) in (b).
[0145] However, it is not realistic to evaluate the solid lubrication behavior of oil well pipe threads in actual wells or simulated wells, both from the perspective of cost and the time required to arrange experiments.
[0146] The solution to this is as follows.
[0147] A weight of about 1 to 3 actual length pins is installed at the upper end of the short pin. Furthermore, the initial setting position of the thread is set to a position where the pin thread is exposed about halfway relative to the sleeve thread. In this way, a weight is applied during tightening, and no weight is applied during loosening. Based on the simulation of actual tightening in the well, the upper and lower limits of the parameters are determined according to actual conditions.
[0148] That is, in the present invention, the initial setting position of the pin thread is intentionally set to the position where the pin thread is exposed from the sleeve thread. Furthermore, in the present invention, a weight equivalent to 1 to 3 actual-size pins is placed on the pin end, and tightening and loosening are evaluated. When tightening, a weight equivalent to 1 to 3 actual-size pins is applied to tighten. It should be noted that the equivalent of 1 pin is assumed for an onshore well, and the equivalent of 3 pins is assumed for an offshore well. When loosening, the weight is hoisted by a bridge crane to adjust the load, including zero load, and the load is reduced to loosen. When loosening, if the weight is applied as it is, the weight becomes a balancer instead, and the pin rises straight without loosening. Therefore, the solid lubricating film becomes a state in which both the sleeve thread and the pin thread are completely undamaged, and it is impossible to simulate the situation that occurs in an actual well.
[0149] Effects of the Invention
[0150] The reagent of the present invention is a reagent in which the main component of the solid lubricant is a metal soap, the main component of the binder resin is a water-soluble or water-dispersible polymer, and the main component of the solvent is water.
[0151] The reagent of the present invention can provide an environmentally friendly reagent based on the above-mentioned configuration without using a reagent set called a diluent, a heavy metal, and a PFAS.
[0152] In addition, the reagent of the present invention can achieve early drying without using a reagent group called a diluent. Therefore, it can be used even in an environment where fireworks are strictly prohibited. PFAS refers to fluorinated acryloyl groups including PFOS and PFOA.
[0153] Furthermore, the agent of the present invention can provide a solid lubricating film having lubricity and corrosion resistance that can withstand use in actual wells. BRIEF DESCRIPTION OF THE DRAWINGS
[0154] Figure 1 It is a figure which shows an oil country pipe and an oil country pipe threaded joint.
[0155] Figure 2 FIG. 1 is a diagram showing a tightening diagram in a conventional laboratory test (a) and a diagram showing an initial setting position at that time (b).
[0156] Figure 3 FIG. 1 is a diagram showing the actual tightening in a well (a) and FIG. 1 is a diagram showing the initial setting position at that time (b).
[0157] Figure 4 Schematic diagram of the tightening diagram, where (a) is the actual well situation and (b) is the situation of the previous laboratory test.
[0158] Figure 5 is a diagram illustrating the conditions of the new laboratory test (weight clamp).
[0159] Figure 6 This is a diagram showing an example of setting a weight under new laboratory test conditions (weight clamp).
[0160] Figure 7 It is a schematic diagram illustrating the setting state of the pin thread and the sleeve thread. Figure 7 In the description, the description of thread teeth etc. is omitted.
[0161] Figure 8 This is a schematic diagram showing an example of a method of applying coating to a tube using a brush. DETAILED DESCRIPTION
[0162] The present invention relates to a solid lubricating film formed on one or both sides of a lubricating surface and an agent for forming the solid lubricating film when two objects made of the same metal are required to slide with high lubrication. The present invention is particularly directed to a solid lubricating film and an agent for forming the solid lubricating film in the lubrication of a thread shape, and further, in the lubrication of an oil well pipe thread.
[0163] Furthermore, the present invention aims to provide corrosion resistance by means of the lubricating film. The present invention aims to achieve sufficient lubrication of the threaded portion even under actual tightening / loosening conditions in oil and gas wells.
[0164] In the present invention, a solid lubricant component mainly composed of metal soap is used, and a water-soluble or water-dispersible polymer is used as a binder resin. In addition, when the solid lubricating film is formed by coating with a reagent, instant drying from coating to drying is not expected. However, a material having early drying properties that can dry within about 30 minutes even when left in the air after coating with a reagent is used as an object.
[0165] The present invention is provided in a state where the coating is covered with a soft film and protected for corrosion prevention. In addition, the present invention utilizes the soft film as a film having a lubricating function to achieve lubrication. Moreover, the present invention is intended to be used as a reagent for making these films. In the present invention, the main focus is on compliance with international agreements on environmental resistance and reagents, and the design is made including early drying properties as practical ease of use.
[0166] In addition, the reagent of the present invention is also intended to be used when there is a malfunction in the well or when overwork occurs. Moreover, the reagent of the present invention is also intended to remove the actual length pins one by one or in units of 2 to 3, recover and arrange them near the well, and clean them, so that they can be used as a film formed on the thread surface for the purpose of rust protection at this time. Removing the actual length pins one by one is assumed for onshore wells, and removing them in units of 2 to 3 is assumed for offshore wells.
[0167] Next, embodiments of the present invention will be described.
[0168] In this embodiment, an oil country pipe is assumed as a metal component having a surface imparting lubricity, but the present invention can also be applied to other metal components.
[0169] (constitute)
[0170] <Reagents>
[0171] The reagent of the present embodiment is a reagent for imparting lubricity and corrosion resistance to the metal surface of a metal component such as an oil well pipe.
[0172] The reagent contains a solid lubricant, a binder resin, and a solvent component, and may contain a small amount of an additional component depending on the situation.
[0173] [Solvent ingredients]
[0174] The solvent component has water as a main component. A lower alcohol having a carbon number of 3 or less is added to the water as an additive. The volume of the additive relative to water is 0.5 or more and 45 or less relative to 100 of the volume of water.
[0175] One of the characteristics of the composition of the solvent of the present invention is that 95% or more of the volume of the solvent is composed of the water and the lower alcohol, and the solvent is a component system mainly composed of water.
[0176] The lower alcohol includes, for example, one or two or more lower alcohols selected from the group consisting of methanol, ethanol, isopropanol, n-propanol, and industrial ethanol.
[0177] As the additive, at least one of ammonia water and primary amine may be contained. The content of at least one of ammonia water and primary amine is set to 2 or less with respect to 100 volumes of water, for example.
[0178] The addition of the above-mentioned lower alcohol, ammonia water and primary amine is added to achieve early drying of the film by taking advantage of their volatility. At the same time, the lower alcohol functions as follows in the solvent of the present invention which is characterized by water solubility, that is, the solvent in which water is the main component. That is, the lower alcohol effectively functions when dissolving the solid lubricant and dissolving the water-repellent solid lubricant. Moreover, the lower alcohol helps the solid lubricant to avoid an extreme association state and be dispersed and dissolved in the entire solvent.
[0179] If 0.5 or more of a lower alcohol having a carbon number of 3 or less is not added relative to 100 volume of water, the water-repellent solid lubricant cannot be dispersed homogeneously and phase separation occurs with water. Moreover, in most cases, the lower alcohol is placed on the water surface. On the other hand, the flash point of the lower alcohol group is low. Considering the situation where the lower alcohol is applied to the lubrication of oil well pipe threads and the situation where the coating is carried out at a well site where fireworks are strictly prohibited. In this case, the lower alcohol is worried that it will become the cause of the fire and may become a very dangerous reagent. Therefore, the upper limit of the addition of the lower alcohol is set to 45.
[0180] Here, the solid lubricating film formed by drying does not contain solvent components represented by lower alcohols. The solvent component is only a problem related to the drying time of the reagent. Therefore, if it is not an environment where fireworks are not strictly prohibited, a large amount of lower alcohol can be used to speed up drying.
[0181] It should be noted that the preferred addition range of the lower alcohol is 20 or less. Although it is also related to the volatility point described later, when it is 20 or less, early drying is easily achieved. In addition, this range can further ensure that the volatility point is above 70°C, or the level of non-combustible treatment can be achieved, thereby making it safe to use the no-smoking and no-fire sites in the well site. In addition, in the case of a poor case when a large amount of lower alcohol is contained in anticipation of early drying, there is the following problem. That is, it is possible to dry too early, increase the heterogeneity of the solid lubricating film, and rupture the film and deteriorate the film quality.
[0182] [Solid lubricant]
[0183] The solid lubricant contains a soap component including at least a metal soap among a metal soap and an alkaline soap component. The metal soap component accounts for 95% or more of the total weight of the metal soap and the alkaline soap component. That is, the main component of the solid lubricant is the metal soap.
[0184] The weight of the metal soap is set to be more than 95% of the total weight of the metal soap and the alkaline soap. When there is a lot of alkaline soap, there is the following concern: sometimes it is also dissolved in the aqueous solvent, the viscosity of the solvent becomes too high, it is difficult to apply uniformly, and the drying of the film is also slowed down. That is, by reducing the alkaline soap component, the above concerns are reduced. However, under the condition that the alkaline soap is zero, the lubrication improvement effect brought by the alkaline soap cannot be expected, so it is preferred to design the components contained.
[0185] At the same time, the condition that the particle size of the metal soap does not exceed the film thickness of the solid lubricating film is set. As a preferred range, the average particle size of the metal soap is preferably 10μm or less. In the case of exceeding the film thickness of the solid lubricating film, it means that the metal soap penetrates the solid lubricating film and exists. In this case, when tightening and loosening with a strong torque, the damage to the solid lubricating film becomes greater than the case where the metal soap is dispersed in the film in the solid lubricating film. For example, there is a concern that significant peeling will occur, and as a result, the lubrication characteristics will deteriorate. Therefore, it is necessary to be less than the film thickness of the solid lubricating film. On the other hand, in the case where the solid lubricating film is assumed to be thin for achieving the film thickness required for lubrication / rust prevention, it has a film thickness of at least about 10μm. Therefore, the particle size is preferably 10μm or less.
[0186] The metal soap and alkaline soap components constituting the solid lubricant include one or more soaps, wherein the soap is a compound formed of a fatty acid selected from the following Group A and a metal element selected from the following Group B.
[0187] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid
[0188] Group B: Na, K, Mg, Ca, Zn
[0189] [Binder resin]
[0190] The binder resin includes a water-soluble or water-dispersible polymer, and is a polymer or copolymer containing 90% or more of a polymer having an acrylate or methacrylate structure based on the total weight of the binder resin.
[0191] The water-soluble or water-dispersible polymer constituting the binder resin is, for example, a polymer composed of one or more monomers selected from the following (1) to (4), or a copolymer containing two or more monomers.
[0192] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0193] (2) monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters and their derivatives among acrylates, methacrylates and their derivatives;
[0194] (3) A monomer grafted with the above (1) or (2);
[0195] (4) A monomer of either or both of a vinyl compound and a urethane compound.
[0196] It should be noted that, in this specification, "a polymer containing a water-soluble or water-dispersible polymer, containing 90% or more of the total weight of the binder resin having an acrylate or methacrylate structure" is handled as follows. That is, in the case of a copolymer, if a part of the copolymer structure also contains a part of the acrylate or methacrylate structure, the binder resin of the copolymer is handled as a "polymer having an acrylate or methacrylate structure" regardless of the weight of the acrylate or methacrylate structure other than the introduced structure.
[0197] If the content is less than 10%, the polymer allowed to be mixed is a polymer that does not form a copolymer with the polymer having an acrylate or methacrylate structure as the subject of this application, that is, a structure having an acryloyl group, a vinyl group, etc. in the monomer is excluded.
[0198] In addition, the reagent of the present invention is a reagent that dissolves in an aqueous solvent, so in addition to the above information, it is a necessary condition that the polymer allowed to be mixed is a composition that is soluble in water. For example, polyamide-imide resins, phenolic resins, urea resins (urea formaldehyde) and the like that are soluble in water can be exemplified.
[0199] The weight of the solvent is preferably 0.7 times or more and 100 times or less the total weight of the solid lubricant and the binder resin, for example, when the specific gravity of the solvent is set to 1 and the volume of the solvent is converted into weight.
[0200] In addition, the weight of the solid lubricant is preferably 0.1 times or more and 1.0 times or less the weight of the binder resin.
[0201] It is preferred that the flash point of the reagent be higher than 60° C. or that the reagent be flame retardant (non-flammable) by adjusting the above components.
[0202] Furthermore, it is preferred that the viscosity of the reagent be 1000 mPa·s or less by adjusting the above components.
[0203] Suitable ranges and preferred ranges of these parameters can be specified as described below.
[0204] First, regarding the weight of the solvent, the lower limit of 0.7 or more is the amount of solvent required to dissolve the solid lubricant. In fact, as shown in the examples described later, the metal soap of the main component of the solid lubricant can be dissolved to 0.7. In addition, in the case of 0.5, it becomes a condition that the lubricating component to be mixed is not fully dissolved, so 0.7 is used as the lower limit. The lubricating component to be mixed refers to the metal soap component, the alkaline soap component, etc. Regarding the upper limit, it is assumed to be less than 100 times, but less than 10 times is the preferred range. A high weight ratio of the solvent means that there are many reagents and thin film components. The film component refers to the adhesive resin constituent component, the solid lubricant component, etc. If you want to repeat the coating and drying, there is no special problem with the upper limit up to 100 times. On the other hand, if you don't mind the trouble of repeated coating and repeated drying, it can be used even if it exceeds 100 times. At the same time, the worry that the film quality is uneven due to the dilution of the reagent becomes higher. Therefore, the number of tightening and loosening is slightly worse, but it can be used sometimes.
[0205] Hereinafter, the “number of times of tightening and loosening” is also described as “number of times of M / B”.
[0206] The preferred range is 10 times or less. When it is 10 times or less, the necessary film thickness can be easily formed with an conceivable coating method, such as 1 to 3 coatings, the M / B times are good, and no particular degradation is found. In the examples described below, it can be confirmed that a solid lubricating film can be formed without problems until the weight ratio is below 7.6, and the necessary lubrication properties can be achieved. Therefore, it can also be said that 7.6 or less is a further preferred range. As described later, with regard to rust resistance, it is also preferred that the solvent weight is low. In the present application, the solvent is mainly water. Therefore, in order to avoid rusting of the insufficiently dried part, it is more preferably less than 2 times.
[0207] Next, regarding the weight ratio of the solid lubricant / the weight ratio of the binder resin, the lower limit is 0.1 times or more and the upper limit is 1.0 times or less, which is a preferred range. When the solid lubricant is less than the binder resin, the total amount of the solid lubricant mainly responsible for lubrication is small, so there is a tendency for lubrication to deteriorate. On the contrary, when there is too much, sometimes more than necessary is contained, the solid lubricants interfere with each other, and the improvement of the lubrication characteristics tends to be saturated or deteriorated. In the examples shown below, the characteristics are actually degraded to a level where the M / B times are counted as the lower limit of the qualified range. Within the scope of the experiment, the lower limit is 0.08 and the upper limit is 5.0.
[0208] The preferred range of the flash point is preferably above 60°C, and it is more preferably defined as a non-flammable classification. On the other hand, in oil / gas wells, depending on the use environment, if there are places or areas where it is used in a temperature range below 60°C, the reagents and films used to make the solid lubricating film of the present application can be used. They are parameters determined purely based on the safety of the operator and the well site. It is not a factor affecting lubrication evaluated by the M / B number. Except for replacing Freon, a low flash point means high volatility in most cases, thus affecting the behavior of early drying and early filmization of the reagent. Considering the use environment in the well, it is set to above 60°C, and it is more preferably designed to be a higher temperature or non-flammable classification.
[0209] The viscosity of the reagent is a parameter that defines the reagent as a result when the reagent is prepared including solvents, solid lubricants, binder resins, and other additives. The viscosity varies according to the concentration of the preparation. In the present application, the viscosity is preferably set to 1000mPa·seconds or less in order to suppress uneven coating and uneven film thickness of the reagent. This is because, when the viscosity is high, the tendency of uneven film thickness becomes higher. In the following embodiments, no degradation is found especially when it is below 740mPa·seconds, so it can be said to be a more preferred range.
[0210] In addition, it is considered that by adjusting the above components, the metal surface is 0.1g / mm 2 In this case, it is preferable to adjust the coating amount of the reagent to have an early drying property that allows the reagent to dry within 30 minutes when left to dry in a windless atmosphere at normal temperature.
[0211] Alternatively, it is considered that by adjusting the above ingredients, the metal surface is 0.1g / mm 2 In this case, it is preferable to adjust the coating agent to have an early drying property that allows drying within 5 minutes when drying in an atmosphere of normal temperature with air flow of 1 m / sec or more.
[0212] It should be noted that the "normal temperature" mentioned here refers to a temperature in the range of 15 to 30°C.
[0213] 0.1g / mm 2 The following coating amount refers to a typical coating amount achieved by a method of applying by rotary coating while pulling a JIS 20 bristle with a bristle width of 50 mm only once in one direction. In addition, the drying time at this time is defined. It is preferably achieved within 30 minutes by leaving it to dry and within 5 minutes by drying with air supply of 1 m / sec or more. This means is achieved using multiple parameters specified in this application. By containing at least one of a lower alcohol and ammonia water and using its volatility and dispersing a metal soap containing a solid lubricant in an appropriate size, the volatile surface area is increased, thereby enhancing drying.
[0214] <Method for producing reagent>
[0215] The reagent is preferably prepared by dispersing the metal soap in a lower alcohol to make it turbid and then adding the resulting dispersion into water as a solvent.
[0216] <How to apply the reagent>
[0217] The reagent is preferably applied after the container containing the reagent is vibrated and stirred before application.
[0218] Furthermore, when applying the reagent of the present embodiment to the surface of the tubular member, it is preferable to apply the reagent in the circumferential direction while rotating the tubular member.
[0219] <Oil well pipe and oil well pipe threaded joint>
[0220] Oil well pipe is Figure 1 The sleeve 2 shown has an internal thread 2a and the pin 1 has an external thread 1a.
[0221] like Figure 1 As shown, the oil well pipe threaded joint includes a sleeve 2 such as a coupling having an internal thread 2a and a pin 1 having an external thread 1a. In addition, a lubricating film having a solid lubricating film of the present invention is formed on the contact surface (fastening surface 10) of the threaded portion of at least one of the sleeve 2 and the pin 1.
[0222] A lubricating film having a solid lubricating film is formed on the threaded portion of the oil country tubular good of the present embodiment.
[0223] The solid lubricating film includes a binder resin and a solid lubricant dispersed in the binder resin.
[0224] The solid lubricant contains a soap component including at least a metal soap of a metal soap and an alkaline soap component, wherein the metal soap component accounts for 95% or more of the total weight of the metal soap and the alkaline soap component.
[0225] The metal soap and alkaline soap components constituting the solid lubricant include, for example, one or two or more soaps that are compounds formed of a fatty acid selected from the following Group A and a metal element selected from the following Group B.
[0226] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid;
[0227] Group B: Na, K, Mg, Ca, Zn.
[0228] The weight of the metal soap is, for example, 95% or more of the total weight of the metal soap and the alkaline soap.
[0229] The particle size of the metal soap is preferably 10 μm or less.
[0230] The binder resin includes a water-soluble or water-dispersible polymer, which is a polymer or a copolymer containing 90% or more of a monomer belonging to acrylate or methacrylate.
[0231] The water-soluble or water-dispersible polymer constituting the binder resin is, for example, a polymer composed of one or more monomers selected from the following (1) to (4). The copolymer is a copolymer containing two or more monomers thereof.
[0232] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0233] (2) monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters and their derivatives among acrylates, methacrylates and their derivatives;
[0234] (3) A monomer grafted with the above (1) or (2);
[0235] (4) Monomers of either or both of vinyl compounds and urethane compounds
[0236] It should be noted that the "water-soluble or water-dispersible polymer, containing 90% or more of the total weight of the above-mentioned binder resin having an acrylate or methacrylate structure" mentioned here is handled as follows. That is, in the case of a copolymer, if a part of the copolymer structure also contains a part of the acrylate or methacrylate structure, then the binder resin of the copolymer is handled as a "polymer having an acrylate or methacrylate structure" regardless of the weight of the acrylate or methacrylate structure introduced. It does not only refer to the weight of the "acrylate or methacrylate".
[0237] The solid lubricating film has a film thickness of, for example, 1 μm or more and 100 μm or less, and is soft with a hardness of H or less in pencil hardness.
[0238] It should be noted that a base film (not shown) may be present as a lower layer of the solid lubricating film.
[0239] The oil country tubular good of at least one of the sleeve and the pin includes the oil country tubular good having the lubricating coating of the present invention formed thereon.
[0240] When one of the sleeve and the pin is an oil country pipe having the lubricating film of the present invention, it is preferable that a film having a higher hardness than the solid lubricating film be formed on the threaded portion of the other oil country pipe.
[0241] The lower limit of the film thickness is 1 μm or more to comply with the film thickness required for lubrication, and the size of the metal soap is determined to be less than the film thickness that does not cause the solid lubricating film to fly off. The upper limit of 100 μm or less is determined by the gap between the internal thread / external screw (coupling / pin) of the oil well pipe thread. It is inevitable that the solid lubricating film will be ground to a certain extent during tightening and loosening. In addition, the source of the ground solid lubricating film moves in a linked manner during tightening and loosening, or is formed again and attached again, or is unable to perform these actions and is blocked in the thread gap. As a result, the concern of burning increases. Although it also depends on the type of thread, the thread gap "the top of the pin and the bottom of the coupling" is about 100 μm. On the other hand, the thread gap "the bottom of the pin and the top of the coupling" is a close-fitting structure. When the solid lubricating film exceeds 100 μm, it is estimated that the absolute amount of the solid lubricating film that is inevitably ground off to a certain extent during tightening and loosening becomes larger, and exceeds the amount absorbed by the above-mentioned gap, and in fact, burning often occurs. Therefore, regarding the upper limit, 100 μm or less is set as a preferred range. When exceeding this range, it is difficult to say that it is always NG, but it is easy to cause burning when the M / B number does not meet the regulations.
[0242] As described above, the reagent of the present invention is set as a binder resin component mainly composed of a water-soluble or water-dispersible polymer. In addition, a metal soap is used as the main component of the solid lubricant, and a trace amount of alkaline soap and other additives that function as solid lubricants are added thereto. Furthermore, the reagent of the present invention includes a component system that allows the addition of a small amount of organic solvent and a solvent with water as the main component.
[0243] The agent of this composition achieves early drying after coating, and further, the solid lubricating film formed by the agent achieves lubrication and rust prevention that can withstand use in the well. In the present invention, as the environment in which it is used, the lubrication of the oil well pipe threaded joint is taken into consideration as the most stringent condition.
[0244] The following describes in detail the definition of each element.
[0245] In the present invention, early drying property, corrosion resistance, and lubrication properties are expected from the agent and the solid lubricating film formed using the agent.
[0246] However, the parameters for achieving each required characteristic are related to the required characteristic and are achieved within the upper and lower limits specified in the present invention. First, the required characteristic as the target is explained, and then the range of each parameter and its meaning are explained.
[0247] "Early drying, corrosion resistance, and lubrication properties as targets"
[0248] The early drying property in the present invention means that the product can be dried within 5 minutes, preferably within 1 minute, by drying with air supply without heating. Alternatively, the product can be dried within 30 minutes, preferably within 15 minutes, and more preferably within 5 minutes when placed outdoors or indoors at room temperature.
[0249] The dryness mentioned here exceeds the dryness to touch level, which means the semi-cured level or the cured dryness level. It should be noted that the coating terms such as dryness to touch and semi-dryness are defined in accordance with JIS K5500-2000.
[0250] However, in the case of an object coated on an oil well pipe threaded structure, the present invention is an invention that targets a reagent with low viscosity and good fluidity. Therefore, it can also be assumed that the coated reagent must be concentrated at the 6 o'clock position, that is, the lowest position, and the liquid accumulates or drips in this part. Therefore, regarding the above-mentioned early drying, the drying state of the threaded position on the upper side of the clock from 8 o'clock to 4 o'clock in the clock is discussed. The portion from 4 o'clock to 8 o'clock, more accurately from 5 o'clock to 7 o'clock, which remains due to the accumulation, dripping, etc. of the reagent, is excluded from the early drying. The reason why there is no problem even if it is excluded is the following reason. That is, this is because the coated reagent is sometimes accumulated in a semi-wet state, but at the bottom layer of the coating liquid applied to this part, there is a portion that constitutes a solid lubricating film, and there is no problem with the soundness of the film from the perspective of rust resistance. That is, this is because insufficiently dried portions remain only in the portion sandwiched between the dried bottommost film from the pipe surface and the topmost film in contact with the atmosphere, and the solid lubricating film formed by drying in the bottommost layer can be realized in terms of rust prevention.
[0251] The corrosion resistance of the present invention does not only mean the corrosion resistance of the surface in the state where water is volatilized and evaporated after the reagent is applied. The corrosion resistance of the present invention assumes a tubular structure with thread teeth such as oil well pipe threads as the most stringent condition. In addition, the present invention targets the corrosion resistance in the state where a protective cover such as a protective device is tightened and loosened, that is, installed once and removed again, and the protective device is removed. Slightly more stringent conditions are assumed compared to the actual required characteristics.
[0252] For actual oil well pipe threads, the following situation can be imagined: after the solid lubricating film is formed, when the protector is installed, the solid lubricating film and the protector partially contact each other, and the film is damaged. This is because the protector is installed in this state and left standing outdoors or indoors.
[0253] In the present invention, the lubrication characteristics are ensured by evaluation results in an actual well or a simulated well, or by evaluation by a tightening test using a power tong that can approximate the evaluation results.
[0254] The present invention does not evaluate the quality of lubricity in the conventional tightening and loosening test using only a short pin. The present inventors have found that the solid lubricating coating cannot be appropriately evaluated in the conventional evaluation using a short pin.
[0255] Here, in the lubrication of oil well pipe threaded joints, the mainstream from the past to the present is the lubrication using lubricating compounds. Since the lubricating compound is in a viscous liquid state, the compound moves in conjunction with tightening and loosening, and plays a role in the direction of making lubrication a good method. Therefore, whether it is the lubrication evaluation in the laboratory using a short pin or the evaluation in the actual well, the evaluation can be performed without much difference. However, in the lubrication based on the solid lubricating film of the present invention, the solid lubricating film is sometimes inevitably ground, and its fragments and powders sometimes cannot move in conjunction with tightening and loosening like the compound. In response to this, it will be described in detail again later that a method for evaluation under conditions close to the actual well was studied in the laboratory, and the feasibility of the solid lubricating film was judged based on the lubrication behavior evaluated in the test of the study.
[0256] "About water-soluble or water-dispersible polymers"
[0257] In the present invention, a water-soluble or water-dispersible polymer is used as the binder resin.
[0258] In the present invention, it is assumed that water will be dispersed, that is, volatilized, and evaporated to form a film, so the polymer of the present invention refers to a synthetic polymer in a narrow sense. The polymer of the present invention excludes pectin, agar, starch materials, cellulose, and natural gum (alginic acid) materials that are well known in natural polymers. In addition, the polymer of the present invention also excludes a semi-dry and moist material that is kept at the stage of drying, that is, water dispersion. In the case of incomplete drying, when the object to be coated is carbon steel, there is a concern that corrosion may be caused by water.
[0259] Specifically, the water-soluble or water-dispersible polymer in the present invention includes a polymer composed of one type and a copolymer composed of two or more types of monomers. Each monomer corresponds to the following monomers (1) to (4).
[0260] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0261] (2) monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters and their derivatives among the acrylic esters, methacrylic esters and their derivatives because they are aqueous;
[0262] (3) A monomer grafted with the above (1) or (2);
[0263] (4) A monomer of either or both of a vinyl compound and a urethane compound.
[0264] The present invention includes a substance comprising a copolymer formed by at least one polymer specified in (1) to (4) or a copolymer containing two or more monomers, or a polymer containing a monomer single substance of (1) to (3), or a polymer containing a copolymer of (1) to (3) or both of them and (4) or other compounds.
[0265] Other compounds refer to monomers such as maleic acid, sulfonic acid, styrene, carboxylic acid and their salts.
[0266] It should be noted that the "polymer containing water-soluble or water-dispersible polymers, containing more than 90% of the total weight of the above-mentioned binder resin having an acrylate or methacrylate structure" described herein is handled as follows. In the case of a copolymer, if a part of the copolymer structure also contains a part of the acrylate or methacrylate structure, the binder resin of the copolymer is treated as a "polymer having an acrylate or methacrylate structure" regardless of the weight other than the introduced acrylate or methacrylate structure. It does not only refer to the weight of the "acrylate or methacrylate". It should be noted that the water-based polymer described herein refers to a polymer that has hydrophilicity by containing polar or charged functional groups in the structure of the polymer. For example, it refers to a substance containing a carboxyl group, an amine functional group, a sulfonic acid, etc. in the main chain or side chain.
[0267] The binder resin of the present invention is dissolved in a solvent containing water as a main component, and when the reagent is applied, the water is scattered, that is, evaporated and volatilized to form a film.
[0268] It should be noted that in the present invention, since there is a basic premise of considering the environment, the reagent of the present invention is designed without using raw materials containing F (fluoro) alkyl groups, which are heavy metals represented by lead and the group called PFAS, which are considered to be problematic recently.
[0269] The regulations for achieving early drying properties of the film after the application of the reagent directly and indirectly affect the film properties of the reagent.
[0270] Next, the project team on early drying properties was explained in detail.
[0271] Preferably, the final film is a polymer or copolymer containing 90% or more of monomers belonging to acrylate or methacrylate. It should be noted that, during copolymerization, a substance containing acrylate or methacrylate and copolymerized with other monomers is considered to be a polymer of acrylate or methacrylate, satisfying the above-mentioned requirement of 90% or more.
[0272] Setting the content to 90% or more means that the majority of the copolymer is composed of acrylate and methacrylate polymers, and adding 10% or less of other polymers is acceptable. In essence, as a copolymer, it is assumed that the content of acrylate and methacrylate polymers is close to 100%.
[0273] "Why early drying is necessary and why the target value is set"
[0274] The reason why early drying properties are required is that there is a reality that only the agent of the present invention is required, and the solid lubricating film formed using the agent is used to form a film at the production site and is also used at the use site.
[0275] In particular, when the application in oil well pipe threaded joints is envisioned, the use of the following reagent is also envisioned. That is, in particular, the use of the reagent is also envisioned when the oil well pipe for pipeline is temporarily lifted due to a fault at the well site, or when the oil well pipe is taken out and transported to the workshop due to a burn. In this case, it is necessary to complete the work in the category of a clean, green solid lubricating film. The oil well pipe extracted from the well is washed with water, etc., and in order to prevent the threaded part from rusting, a solid lubricating anti-rust film can also be formed using the reagent of the present invention. Such a demand is natural in the use at the well site.
[0276] At this time, when using a conventional wet compound, a storage compound is often applied. For example, KENDEX TM , OCTG ORANGE CORROSION INHIBITOR & STORAGE COMPOUND, etc. In addition, in the absence of a storage compound, a lubricating compound with heavy metals Pb and Zn added is applied for rust prevention. In this case, it is not green either. In other words, a material with harmful heavy metals added is used.
[0277] In contrast, in the present invention, since it is an agent for forming a solid lubricating film, it is assumed to be applied in the environment of a well site. That is, in the present invention, it is required to dry into a solid lubricating film as early as possible in an environment where pyrotechnics are strictly prohibited without using components that may cause fires, including heaters, etc.
[0278] From another point of view, when thread grinding is performed on-site, there are situations where the production system of each workshop has defects.
[0279] The workshop that performs thread grinding has sufficient equipment for machining. In the case of the conventional method of using a compound, the surface treatment of the sleeve thread is mostly outsourced and rarely owned by the manufacturer. The surface treatment is performed by, for example, phosphoric acid Mn treatment, Cu plating, etc. At the same time, for the pin thread, it is not required to apply the viscous liquid storage compound and then dry it. Therefore, the pin thread is usually shipped directly with the protective device installed after the coating without going through the drying process.
[0280] When the reagent of the present invention is used on site, it is judged that it is difficult to expect a dryer or a heat treatment device for air supply or hot air. Therefore, as the reagent of the present invention, it is judged that it is necessary to dry it by placing it indoors or outdoors for less than 30 minutes, preferably 15 minutes, and more preferably within 5 minutes.
[0281] 30 minutes is a time when an operator repeatedly performs the following operations: about 30 pin threads and sleeve threads are spread out and arranged, and one end of each oil well pipe is coated sequentially from the end, and then the end on the opposite side is coated sequentially from the end. Moreover, 30 minutes is a time when it is assumed that the pipe is almost dry when it returns to the original position. In addition, it is set to a time when the protective device is prepared and tightened sequentially without waiting time. If the drying time is 15 minutes, there will be no problem even if a small number of threads are processed. Drying in less than 5 minutes is the most preferred goal.
[0282] However, in factories that manufacture products with lubricating films, etc., air supply equipment and the like can be expected. Therefore, drying can be promoted not only by leaving the product in the atmosphere, but also by air supply equipment such as jet fans, air supply equipment for heaters that send out hot air, heat treatment furnaces, etc. In this case, it is preferred to dry the product within 5 minutes, within 3 minutes if possible, and more preferably within 1 minute. In order not to hinder the production line speed and processing at the site of manufacturing products with solid lubricating films having excellent lubrication / corrosion resistance, or even if hindered, to keep the drying time at a low level, it is preferred to set the drying time within this degree.
[0283] It should be noted that when explaining the air volume of a fan or blower, the air volume of an electrically-activated fan is usually 2 to 4 m / s. However, the present invention assumes that drying can be performed even with a weak hand fan, so the drying time is evaluated by assuming drying with an air flow of 1 m / s.
[0284] "Method of applying reagent"
[0285] The basic composition of the reagent of the present invention is a solvent (water + trace amounts of lower alcohols, ammonia, and primary amines), a binder resin (mainly a water-based polymer), and a solid lubricant (metal soap + trace amounts of alkaline soap).
[0286] The viscosity of the reagent is also an important parameter. Moreover, as an element for achieving early drying, it is preferred to design the liquid so that the viscosity of the reagent is close to the lower side. In this case, if applied to an inclined surface, it is more likely to feel flowing than if it stays there. That is, as the viscosity of the reagent, it is preferably adjusted to a viscosity that allows a feeling of flowing after application.
[0287] For example, the viscosity is preferably below 1000 mPa·seconds. This level is a level at which it feels like the agent is flowing along the slope when applied to an inclined member or tubular member. It should be noted that the viscosity of the present invention refers to the viscosity of the reagent in the unsealed state or at the beginning of the application. By stipulating this viscosity, it is possible to avoid accidentally forming a thick film when applying the reagent. The lower limit of the viscosity is not set, for example, it is set to 40 mPa·seconds or more. When a water-soluble or water-dispersible polymer material is added to prepare an aqueous solvent, the viscosity of water is not reached: 1 mPa·second, and there is a tendency for the viscosity to increase. Therefore, the lowest viscosity is also about 40 mPa·seconds.
[0288] By setting the viscosity of the reagent to 1000 mPa·s or less, there is the advantage that when overlapping coating or thick coating is difficult, the coating thickness can be made uniform and thin. The viscosity can be adjusted by adjusting the selection of monomers constituting the water-based polymer, the concentration of the metal soap and the alkaline soap, and the mixing ratio including the solvent.
[0289] On the other hand, since the viscosity of the reagent is less than 1000 mPa·second, it has low viscosity and is easy to flow. Therefore, the reagent in the dry part tends to drip and accumulate at the 6 o'clock position on the clock. Moreover, since this part accidentally becomes a thick film, even if the base is dried and film-formed, sometimes only the accumulated part does not dry within the above drying time.
[0290] Therefore, regarding the above-mentioned drying time target, if the lubrication is for a tubular structure, the drying condition of the upper half at 12 o'clock on a clock, or more generally, at 9 o'clock to 3 o'clock, is observed. There is indeed liquid accumulation at the 6 o'clock position, but it is only the undried agent that accumulates on the dried part. Therefore, the lower part dries at the initial stage of coating.
[0291] About coating method, brushing, spraying, dipping and hand coating, mechanical coating and other methods are all allowed. The following process can also be adopted: actively and effectively utilize the tendency of liquid dripping, after coating, in a way that the coating flows downward, the object coated with the reagent is tilted downward or obliquely. In addition, when the metal part is a tubular part, it is preferred to rotate the metal part while utilizing bristles and spraying to coat it compared with static coating. Thus, drying is also strengthened, and the remaining amount of the unfilmed reagent is uniformly coated on the metal surface again while rotating, which helps to form a uniform film. In addition, it is also possible to avoid accumulating in one part.
[0292] "Study for achieving early dryness"
[0293] In the present invention, in order to achieve early drying properties of a water-soluble or water-dispersible polymer, essential and preferred structures including the following four structures are examined and effectively utilized.
[0294] <Required components>
[0295] One of the essential components is a lower alcohol.
[0296] That is, in order to enable use even in an environment where fireworks are strictly prohibited, the lower alcohol is effectively used as a volatile organic solvent whose concentration is adjusted to a flash point of 60°C or more, and early drying is achieved. The concentration can be adjusted until the flash point of the reagent is preferably 150°C or more, more preferably 250°C or more. It should be noted that the use of VOC diluents is avoided. This is to avoid the safety and health of the operator and the construction of exhaust equipment such as ventilation, etc., so that the operation can be carried out.
[0297] Another candidate is ammonia.
[0298] Depending on the situation, the volatility of ammonia water can also be effectively utilized to control its concentration within an appropriate range at a level that does not require the use of ventilation equipment.
[0299] One of the components is the concentration and particle size of the metal soap.
[0300] The concentration and particle size of the metal soap contained are controlled within an appropriate range to achieve early drying. The particle size of the metal soap is set to be 10 μm or less. By using a metal soap with a particle size of preferably 5 μm or less, more preferably 1 μm or less, the surface area of the metal soap can be increased to enhance drying.
[0301] At this time, it is necessary to consider how to prevent the metal soaps from agglomerating with each other and from becoming larger than their respective sizes. This is achieved by dissolving the metal soap and the lower alcohol once and then mixing them into a mixed solution of a solvent consisting of water and a water-based polymer.
[0302] The metal soap also functions as a main component of the lubricant, and 95% or more of the total weight of the solid lubricant together with the alkaline soap described below is composed of the metal soap. Regarding the overall mixing ratio, when the material is observed as a solid lubricating film after the solvent is volatilized and evaporated, the total weight of the solid lubricant accounts for 0.05 to 1.0 relative to 100 of the weight of the binder resin. It should be noted that 95% or more of the total weight of the solid lubricant is composed of the metal soap.
[0303] The present invention can use alkaline soap as a support for lubrication. However, the addition of soap that is easily soluble in water tends to cause water as a solvent to become a gelled state with high viscosity. Therefore, there are adverse effects such as increased viscosity of the reagent and time spent on film formation. If it is over-gelled, it is impossible to completely dehydrate and a solid lubricating film cannot be formed in a dry state. Therefore, it is necessary to set the upper limit of the appropriate amount of alkaline soap at a trace level. Moreover, it is made into the range of the following appropriate viscosity range. Moreover, the metal soap as the main component in the solid lubricant as described above is made to be more than 95%, that is, the alkaline soap component is made to be less than 5% as the upper limit.
[0304] The viscosity of the reagent was adjusted to 1000 mPa·s or less.
[0305] When water-soluble or water-dispersible polymer materials, additives such as metal soaps, and the above-mentioned lower alcohols are prepared as reagents, this viscosity is required. In short, the viscosity is to form a low-viscosity, dry liquid viscosity. The lower limit of the viscosity is not set, but it is generally above 40mPa·second. When a water-soluble or water-dispersible polymer material is added and prepared into an aqueous solvent, the viscosity of water is not reached: 1mPa·second, and the viscosity is high. Moreover, its level is approximately 40mPa·second.
[0306] <Preferred Configuration>
[0307] When applying the reagent to the tubular metal part as a structure, it is preferred that the coating be performed while rotating the tubular structure. It is preferred that the rotation be continued even after the coating. This is because the undried reagent after the coating will not accumulate at 6 o'clock due to the rotation, and the same effect as the drying promotion achieved by air supply, etc. can be expected.
[0308] In addition, in the case of a tubular metal part (structure), the liquid accumulates at the 6 o'clock position anyway, and it takes time to dry only the outermost layer. It takes a long time until the entire surface is completely dried. Therefore, when applying to the outside of the tube, it is preferable to effectively use the dripping from the 6 o'clock position. Alternatively, whether on the outside or inside of the tube, it is preferable to effectively use the tube to tilt and discharge the reagent that tends to accumulate at the 6 o'clock position to the outside.
[0309] In addition, early drying can also be achieved by effectively utilizing a drying process such as drying with an air blower, drying with a hot air blower, infrared irradiation, ultraviolet irradiation, heat treatment, etc. In this case, a synergistic effect with the case of adopting the above-mentioned configuration can also be expected.
[0310] "Effective use of lower alcohols, ammonia or primary amines, and flash point of the reagent as a whole"
[0311] In the present invention, the volatility of lower alcohol and ammonia is effectively utilized, and the size of the metal soap as the main component of the solid lubricant is selected to be fine. As a result, the surface area is increased and early drying is performed, and the viscosity of the agent itself is reduced and the fluidity is high. Thus, thick film formation is avoided and the volatilization and evaporation of water are promoted.
[0312] The lower alcohol referred to herein refers to, for example, one or a combination of two or more selected from methanol, ethanol, isopropanol, n-propanol, and industrial ethanol.
[0313] Among lower alcohols, alcohols with more than 4 carbon atoms, i.e., butanol and above, tend to be difficult to dissolve in water. Therefore, in the present invention, lower alcohols with less than 3 carbon atoms are used. However, they have low flash points at high concentrations and cannot be used in environments where fireworks are strictly prohibited. Therefore, the reagent is prepared in such a way that the flash point of the final prepared reagent is above 60°C, preferably above 150°C. It is further preferred to prepare it to a level that can be classified as non-flammable. The lower alcohol group contains a minimum of 0.5% or more, thereby effectively utilizing volatility and achieving early drying. The most preferred situation is that the flash point is not established and cannot be measured, which is defined as a non-flammable state.
[0314] The lower alcohol group has the following functions: while being used to strengthen drying, it also prevents the metal soap of the additive from agglomerating and preventing it from agglomerating in the size at the time of input, and allows for formulation.
[0315] If only the metal soap is dissolved in water, the water repellency will be affected, the metal soap will not be mixed into the water, and will be associated with each other to form lumps. Therefore, even if you want to mix the metal soap with a particle size below the specified value into the coating, if you mix the metal soap directly into the water, it will not be fully dispersed. Therefore, even in the state of forming a film, it is a film with deviations, which is not good for lubrication and corrosion resistance.
[0316] The present invention first adds a dissolved metal soap to a lower alcohol. Then, a method is adopted in which a substance in a state of mixing lower alcohol and metal soap is mixed into a dispersion of a water-soluble or water-dispersible polymer and water. At this time, the concentration of the lower alcohol and the content of the metal soap need to be adjusted to fall within the range specified in the present invention.
[0317] In addition, in order to strengthen early drying, the volatility of ammonia and primary amines can be further effectively utilized by mainly using lower alcohols.
[0318] The ammonia mentioned here refers to aqueous ammonia. The commercially available reagent is prepared into 28-30% aqueous ammonia. Incidentally, aqueous ammonia itself is non-flammable. It should be noted that, regarding aqueous ammonia, as commercially available aqueous ammonia, there are also relatively dilute aqueous ammonia at 10% or 5%. However, in the present invention, the conversion study is based on concentrated aqueous ammonia (28-30%).
[0319] Aqueous ammonia is sometimes used as a reagent for preparing aqueous polymers at a neutral pH range, specifically, at a pH of about 5 to about 9. Aqueous ammonia can be used together with the volatilization effect of lower alcohols.
[0320] It should be noted that the use of primary amines belonging to the group with high volatility is permitted under the condition that the pH does not exceed the above-mentioned pH. The primary amine can be added in such a way that the pH is biased toward the alkaline side. Moreover, the ammonia and primary amine added to bias the pH from the neutral side to the alkaline side are used to effectively utilize volatility.
[0321] However, care must be taken in handling primary amines, especially methylamine. Aqueous ammonia can be treated as non-flammable. On the other hand, methylamine is highly flammable, so if added in large quantities, there is a high risk of accidents. Therefore, primary amines can be used in small amounts, but care must be taken in handling them. In order to enhance drying by volatilization, the weight of the lower alcohol group, ammonia, and primary amines must be less than 30% relative to the total solvent. The upper limit is limited by the flash point, etc.
[0322] The reagent of the present invention does not contain freon substitute solvents that are poorly soluble in water, halogenated solvents such as trichloroethylene and tetrachloroethylene, and reagents called diluents. These reagents are not suitable for use due to the global environment and health problems. In addition, among VOCs, the reagents called diluents are mostly harmful to health and are classified into toluene, xylene, benzene, mineral spirits, ether groups, and oils widely called mineral oils.
[0323] The reason for setting the flash point of the reagent of the present invention to 60°C is as follows. In an actual well site, the temperature that can be assumed to be generated when the oil well pipe threaded joint is laid while being tightened is considered to be less than 60°C at the highest. Therefore, it is not lower than this temperature in the first place. Thereby, the risk of ignition and fire caused by volatile reagents is reduced to essentially zero. The preferred flash point is set to 150°C and the more preferred flash point is set to 250°C for the following reasons. That is, as the temperature of the well site, as the highest temperature measured by the thermometer at the bottom of the well, 250°C is sometimes assumed, and as the highest temperature that can be assumed to be the temperature of the well site after heat transfer, 150°C is sometimes assumed, so it is set in this way. In order to make the risk level zero, it is impossible to measure the flash point, and it is classified as non-flammable.
[0324] "Metallic soap particle size and concentration, alkaline soap content"
[0325] In the present invention, metal soap and alkaline soap function as solid lubricants. Furthermore, in order to enhance early drying, metal soap is reduced in particle size to increase surface area and promote drying. Alkaline soap is temporarily dissolved in the main solvent of water and then enters the film, or appears on the surface of the film or precipitates inside the film. However, alkaline soap is not liquid in the end, so it is treated as a solid lubricant.
[0326] In the following description, the solid lubricant refers to a substance containing a soap component of a metal soap and an alkaline soap.
[0327] In the present invention, the enhancement of early drying is achieved by achieving multiple factors simultaneously. The additives including the above-mentioned volatile lower alcohol group, ammonia and primary amine are added to the solvent in an appropriate amount to effectively utilize their volatility. Moreover, based on promoting the volatilization and evaporation of the aqueous solvent, the size of the metal soap is specified and it is uniformly dispersed without agglomeration. In addition, in order to prevent the reagent from being applied too thickly, the viscosity of the reagent is set to less than 1000mPa·second. At the same time, in order to achieve lubricity and corrosion resistance at the same time, it is necessary to adjust the addition amount of the metal soap and the alkaline soap.
[0328] Regarding the particle size of the metal soap, a metal soap with an average size of less than 10 μm, preferably less than 5 μm, and more preferably less than 1 μm is used. As a result, the surface area of the metal soap is increased, thereby enhancing drying. The smaller the particle size of the metal soap, the faster the agent dries. However, it is important that the metal soaps are dispersed with each other, the particle size of the metal soap is maintained, and the metal soap does not agglomerate. At the same time, in order to achieve the soundness of the solid lubricating film, it is necessary to make the particle size of the metal soap not exceed the film thickness of the solid lubricating film. When the film thickness is exceeded, the metal soap is felt to protrude from the film. Moreover, when a strong torque is applied, damage to the film, i.e., peeling, grinding, etc., becomes greater.
[0329] On the other hand, since alkaline soap is soluble in water, there is no regulation on the size.
[0330] Metal soap is the main component of solid lubrication and is the key to strengthening drying. On the other hand, alkaline soap is formulated to assist lubrication.
[0331] In actual wells, when a pin of actual size is set in the sleeve thread, it is rare that the pin thread is inserted straight into the sleeve thread and the thread teeth of the pin thread are inserted into the sleeve thread by manual tightening as imagined in an ideal state. In reality, the pin thread is inevitably set slightly tilted. Therefore, even if the pin thread is set by manual tightening, it can only be set in a state where the thread teeth of the pin thread are exposed by about half. Therefore, in the initial stage of tightening with pliers, there is uneven contact between the threads, which can easily cause damage to the surface of the solid lubricating film. At this time, alkaline soap is expected to provide lubrication support such as sliding from a state where the sleeve thread and the pin thread are fully engaged to a stable position. Figure 3 Before the torque rises as shown, in order to prevent the torque from rising like a spike, lubrication is expected to slide into a stable position by using alkaline soap.
[0332] Furthermore, metal soap has water repellency. Therefore, even when the solid lubricating film is slightly damaged, it can be expected that the corrosion resistance can be effectively improved due to the water repellent effect. In other words, the corrosion resistance is ensured by the metal soap.
[0333] Solid lubricants account for more than 95% by weight of metal soap and alkaline soap. In general, about 5% of other solid lubricants are allowed to be mixed, but it is intended that the majority of solid lubricants are composed of materials that are widely classified as soaps.
[0334] As described above, the content of metal soap and alkaline soap is considered from the balance of all reagents. In this case, when the specific gravity is set to 1 and the volume of the solvent is converted into weight, it is formulated to account for 0.7 to 100 times the weight of all solid lubricating components that form the film. The weight of all solid lubricating components is composed of the weight of the solid lubricant and the binder resin. That is, the solvent with water as the main body allows the formulation range in a wide range except for the obviously concentrated or diluted state. When it exceeds 100, there is too much water and it is difficult to dry. In addition, since water itself may become a source of rust, it is preferably less than 10 times, and more preferably less than 2 times.
[0335] Since the solvent does not scatter during the drying process, the substances present as the film are the binder resin component and the solid lubricant.
[0336] The weight ratio of the solid lubricant relative to the weight of the binder resin is 0.01 to 1 times, and it is preferably formulated so that the weight of the metal soap in the solid lubricant accounts for more than 95%. The lower limit is 0.1 times because, when it is less than 0.1 times, the part supporting the solid lubrication is too small, and the improvement effect of lubrication cannot be expected. In this case, when a force is strongly applied to the binder resin, the possibility of the film being peeled off without leaving any residue increases. As a result, the concern about burns increases. The reason why the upper limit is 1 times is that, relative to the solvent, there are too many metal soap components, the soundness of the film itself disappears, and under less load, the film ruptures and the concern about exposure to the environment increases significantly. In addition, in order to prevent the metal soap from agglomerating and maintain a fine-sized metal soap, it can be said that this concentration is the limit.
[0337] "About the types of metal soap and alkaline soap"
[0338] In the present invention, the metal soap and the alkaline soap are assumed to be the following. That is, the metal soap and the alkaline soap are composed of one or a combination of two or more soaps including a compound formed of a fatty acid of Group A and a metal element of Group B described below.
[0339] Group A (stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid)
[0340] Group B (Na, K, Mg, Ca, Zn)
[0341] In the present invention, the metal soap is composed of one or more metal salts of Mg salts, Ca salts, and Zn salts of group B with respect to the fatty acid of group A. The metal salt of the alkaline soap is composed of one or two metal salts of Na salts or K salts of group B.
[0342] There are other commercially available alkali metal salts, but other metal salts are not used in so-called water-soluble applications for cleaning, so they are excluded.
[0343] "Amount of reagent applied and drying time"
[0344] In the above, it is explained that early drying enhancement is achieved by achieving multiple factors simultaneously. That is, based on the restriction that the flash point does not become too low, an appropriate amount of the above-mentioned volatile lower alcohol group, ammonia and primary amine are added to the solvent. Moreover, based on the effective use of their volatility to promote the volatilization and evaporation of the aqueous solvent, the size of the metal soap is reduced, and the metal soap is uniformly dispersed without agglomeration. In addition, in order to prevent the reagent from being applied too thickly, the viscosity of the reagent is adjusted to less than 1000mPa·second.
[0345] Furthermore, as a condition for reliable early drying, under the above conditions, the actual drying temperature is 0.1 g / mm 2The following coating amounts are preferably applied uniformly for early drying. Under these conditions, when left at room temperature in the atmosphere, it can be expected to dry within 30 minutes at room temperature (15°C-30°C, for example, 24°C). In addition, in the case of air drying, when drying is performed by air blowing at 3 mm / sec or more, early drying properties that can dry within 5 minutes at room temperature can be expected.
[0346] The coating amount is, for example, 0.2 to 0.05 g / mm 2 The preferred range is 0.05 g / mm. If the coating is thicker than this, the drying time tends to be slow and the coating will sag anyway. In addition, sometimes only the surface layer of that part does not dry. In addition, if the coating exceeds 0.05 g / mm 2 , there is a tendency to dry faster and the corrosion resistance is sometimes unstable.
[0347] "Film properties: film thickness, pencil hardness"
[0348] In the present invention, when the agent dries to form a solid lubricating film, the film thickness is preferably in the range of 1 μm to 100 μm and is soft with a pencil hardness of H or less.
[0349] Originally, a uniform film thickness of about 10 μm to about 50 μm is sufficient. However, when a reagent having the viscosity described above is applied, since the viscosity is relatively low, no matter how the drying is strengthened, there is a tendency for the coating that cannot be filmized to droop and move. If it is a structure with threads such as the oil well pipe thread structure, there is also an undeniable tendency for the reagent to accumulate at the bottom of the thread, especially at the 6 o'clock position on the clock. In addition, due to the surface tension of the reagent, there is also a tendency for the corner portion of the top of the thread structure to become thinner. Therefore, in order to take into account both lubrication and corrosion resistance, it is preferred to make the film thickness within the above range. When the thinnest part is less than 1 μm, the concern about burns becomes higher. In addition, when it exceeds 100 μm, there is a tendency for the peeling flakes and powdery substances to be ground during lubrication and become the cause of burns. In addition, there is also the possibility of burning due to peeling without leaving any.
[0350] Here, as described above, the film thickness is the film thickness at the stage when the reagent dries and becomes a solid lubricating film. The film thickness is determined, for example, by observing each cross section obtained by cutting along the length direction at four locations along the circumferential direction of the threaded portion (for example, four locations every 90 degrees) with a microscope. Through this observation, the film thickness of each of the thickest and thinnest portions of the film is determined. Then, it is confirmed whether each film thickness is within the above range.
[0351] It should be noted that, when the tendency of the film thickness distribution is known based on past measurement results, the film thickness can be estimated as follows. That is, if the coating and drying methods of the reagent are the same, the maximum and minimum values of the film thickness of the entire threaded portion can be estimated by measuring the film thickness of a predetermined specific location using an electromagnetic film thickness meter.
[0352] The hardness of the solid lubricating film is preferably a pencil hardness of H or less.
[0353] This is because the solid lubricating film of the present invention is formed into a soft film quality, and it is assumed that the solid lubricating film itself is slightly ground at the place where it is strongly touched, thereby achieving lubricating properties. In addition, when the pencil hardness exceeds H and is hard, there is a high concern that it may be completely peeled off and burns may occur.
[0354] It should be noted that the determination of film hardness is based on pencil hardness. The determination method is determined by the method specified in JIS K 5600-5-4 (1999). This standard is translated into "ISO / DIS 15184, Paints and varnishes-Determination of film hardness by pencil test" standard and written in the JIS standard. The test method of pencil hardness of the present invention is evaluated based on the provisions in the JIS standard. That is, 6B~B~HB~F~H~9H are the evaluation objects, and the hardness above 9H is evaluated as ≤6B and ≥9H respectively.
[0355] "The case where the oil well pipe constituting the threaded joint is coated on both sides, the case where it is coated on one side, and the case where it is coated on one side but another type of solid lubricant film exists on the opposing surface"
[0356] The present invention includes both the case where the solid lubricating film of the present invention composed of the agent of the present invention is applied to both sides of the lubrication symmetric surface and the case where it is applied only to one side without any application on the other side.
[0357] When the solid lubricating film of the present invention is formed on only one component, the pencil hardness of the solid lubricating film of the present invention is preferably softer than other types of lubricating films located on the opposite surface. The solid lubricating film of the present invention is designed to be a soft film. During lubrication, it is assumed that the lubricating properties are achieved by slight grinding, so this effect cannot be achieved when the solid lubricating film itself is hard.
[0358] "Evaluation method for corrosion resistance of solid lubricating films"
[0359] In the corrosion resistance evaluation of the present invention, a protective device used to protect the thread teeth is temporarily tightened on a structure having a thread tooth structure such as an oil well pipe thread, and then loosened, and then salt water spray is applied to the solid lubricating film with the protective device removed. Then, the sample with red rust on the entire surface is judged as NG. In short, as an evaluation of corrosion resistance, an evaluation using salt water spray is performed after temporarily causing conceivable damage to the film.
[0360] It should be noted that the salt spray conditions were determined by the method of JIS K 5600-7-1 under 5% NaCl neutral salt spray conditions (35°C, humidity 98-99%, spray 1-2 mL / Hr / 80 cm 2 , pH 6.5-7.2), based on 8 hours of evaluation.
[0361] Here, the metal surface of the metal parts that are the subject of the present invention includes, for example, surfaces after lathe processing, grinding processing, and polished surfaces. It should be noted that, as a corrosion resistance evaluation, the portion of the residual rolling oxide scale is removed. Depending on the roundness and eccentricity of the tubular structure, there may be a sample containing rolling oxide scale in the thread structure. However, with respect to the rolling oxide scale, when cleaning is performed before forming a solid lubricating film, water may enter the tiny defects, holes, and damaged parts of the rolling oxide scale. Moreover, when a solid lubricating film is formed thereon, even if the solid lubricating film is sound, pitting rust may sometimes be generated from the steel of the base. However, this pitting rust is not rust of the solid lubricating film, and is therefore excluded from the evaluation.
[0362] "Lubrication Evaluation Methods"
[0363] In the environment where the solid lubricating film of the present invention is used, the most severe lubrication conditions are adopted, that is, the lubrication is evaluated under the tightening and loosening conditions of the oil well pipe threads tightened in the actual well.
[0364] However, it is not realistic to evaluate the solid lubrication behavior of oil well pipe threads in actual wells or simulated wells, both from the perspective of cost and the time required to arrange experiments.
[0365] Therefore, in the present invention, use Figure 5 and Figure 6 The devices shown were evaluated.
[0366] This solution can load the upper end of the short pin by installing a weight of about 1 to about 3 pins of actual length. In addition, the initial setting position of the thread is made so that the pin thread is exposed about half relative to the sleeve thread for tightening using pliers. At this time, a weight is applied during tightening, but a weight is not applied during loosening to make the pin thread unstable, simulating the tightening conditions in the actual well. In this way, the upper and lower limits of each parameter regarding the lubrication characteristics can be set to values that meet actual conditions. Hereinafter, this evaluation method will also be referred to as "evaluation using weight pliers". It should be noted that, according to the findings of the inventors, it has been confirmed that the evaluation using weight pliers can fully reproduce the evaluation during tightening and loosening in the actual well.
[0367] The background of using the evaluation using the weight tongs is as follows. That is, this is because, when the evaluation using the horizontal power tongs using the short pin of about 1 m in length or the evaluation using the vertical power tongs using the short pin alone is relied upon, the "solid lubricating film evaluation" that is the object of the present invention is mistakenly evaluated as excellent. That is, it can be said that the upper and lower limits of the parameters defining the invention become meaningless.
[0368] Regarding the solid lubricating film, it is sometimes inevitable to damage the solid lubricating film during tightening and loosening, and the peeling pieces and powdery peeling materials do not always move in conjunction with tightening and loosening. In the case of no linkage, they are blocked in the thread gap and induce burns. However, in the previous evaluation using short pins, since it is difficult to be damaged, there is a concern that the originally defective situation will be evaluated as good. On the other hand, in the previous lubrication using composites, since the composite is a viscous liquid, the composite moves in conjunction with tightening and loosening. Therefore, the evaluation results using short pins do not deviate much from the evaluation in the actual well.
[0369] In past patent documents, in lubrication tests based on solid lubricating films, even in the case of large diameter sizes such as 9-5 / 8” and 13-3 / 8”, it is often stated that the number of tightening and loosening can be 15-20 times. However, in the case of solid lubricating films that have inferior lubrication properties compared to grease-like compounds, this number is essentially impossible. It is believed that these are the results of evaluations based on the use of short pins and horizontal or vertical power tongs, which are common in laboratories. In this case, the values of this characteristic evaluation are possible, but in the actual tightening and loosening of wells, in the case of large-diameter oil well pipes using solid lubricating films, there are rarely results at the level of 15 to 20 times.
[0370] Based on the above considerations, in the evaluation method in the examples described below, by using Figure 5 and Figure 6 The simulation is to simulate the tightening and loosening test under the conditions that simulate the actual well and the simulated well. Figure 3 , Figure 4 The lubricity of the solid lubricating film was evaluated under the tightening conditions observed in (a).
[0371] What actually happens in actual wells is that, because it is an actual-sized pin (a pin of more than about 12m), it is not possible to "set the pin completely straight" during the initial setting, and the pin is almost always inserted at an angle. For the actual length of the pin thread, whether you use a centering guide or a compensator to try to set it straight, it is impossible to set it ideally straight. The pin thread is set at a slight angle. In reality, it never happens that the thread teeth of the pin thread can be tightened to the point where they are blocked by the sleeve thread. At the position where the pin thread can be inserted into the sleeve thread and further tightened by manual tightening, the thread teeth partially touch each other halfway. Therefore, when the thread teeth of the pin thread are more than 5 teeth, or when about half of the total thread teeth are exposed, no further progress will be made. Therefore, at the beginning of tightening with pliers, rotate a few times, for example, in Figure 3 The thread is rotated about 6.3 times until the load increases, and then the pin thread and the sleeve thread begin to mesh at the correct position. In the oil well pipe thread, it has a tapered structure like many thread-like structures, so the thread can finally mesh at a stable position. If it is exaggerated, Figure 7 In the figure, the portion surrounded by the circle is severely damaged. Moreover, cracks, peeling, etc. will inevitably occur in the film at a microscopic level. That is, since the pin thread 1a is set slightly tilted, the following situation occurs in relation to the thread portion 2a of the sleeve thread 2. There is a tendency for the position where the pin thread touches to be severely damaged at the front end of the pin thread 1a, near the middle of the thread teeth of the thread portion 2a of the sleeve thread, near the center of the pin thread 1a, and near the entrance of the thread portion 2a of the sleeve thread. "Near the middle of the thread teeth" refers to the vicinity of the position where the pin thread touches the sleeve thread when inserted. "Near the entrance of the thread portion 2a of the sleeve thread" refers to the vicinity of the entrance of the sleeve thread 2a when the pin thread is inserted.
[0372] Figure 3In the process, a spike-shaped torque is observed to rise irregularly several turns before reaching the stable position, that is, before the stable torque rises. This directly leads to the damage of the solid lubricating film due to the uneven contact between the pin thread and the sleeve thread. In view of this, it is necessary to conduct a lubrication evaluation of the solid lubricating film. The solid lubricating film is inevitably ground by the uneven contact between the threads. The peeling pieces and fragments do not necessarily move in conjunction with the tightening / loosening of the threads. Moreover, if the fragments are blocked in the thread gap, it becomes a major factor in burning. The looseness caused by the initial setting position of the pin thread and the dead weight of the actual length pin are superimposed. As a result, the uneven and biased load contacts the pin thread and the sleeve thread, causing the solid lubricating film to inevitably peel off or become powdery. In addition, the evaluation is performed by simulating the effect of them being blocked in the thread gap and burning in the laboratory.
[0373] Figure 5 This is the overall concept diagram of the test method. Figure 6 This is an enlarged view of the portion involved in the weight 3. In the weight tong test, a vertical power tong 4 is used. The short thread 1 and the sleeve thread 2 are tightened by the thread teeth of the pin thread portion 1a and the thread teeth of the sleeve thread portion 2a. At this time, in order to simulate the situation where the threads are not meshed, the initial temporary tightening position is set so that the pin thread portion 1a appears to be exposed from the sleeve thread 2 by half of the total number of threads. This becomes one of the causes of loosening. Tightening with the power tong 4 is started from this state.
[0374] At this time, a weight 3 is installed on the side of the pin 1 opposite to the tightening thread. The weight of the weight 3 is calculated based on the outer diameter and wall thickness of the actual size pin as a load equivalent to 1 to 3 actual size pins. If it is 9-5 / 8" 53.5#, 1 pin is about 1 ton (2200Lb), and if it is equivalent to 3 connections, it is about 3 tons (6600Lb). The equivalent of 1 pin is the assumption of an onshore well, and the equivalent of 3 pins is the assumption of an offshore well.
[0375] like Figure 6 As shown, Figure 5In the weight 3, the insertion rod 13 is joined to the weight body 3A by welding at the axially symmetrical position of the weight. The insertion rod 13 is inserted from the upper side of the pin 1, and the weight is installed on the upper end of the pin 1. Through holes 1d and 13a are pre-opened in the pin 1 and the insertion rod 13. In order to integrate the weight 3 with the pin 1, the through rod 12 is inserted into the through holes 1d and 13a. The swivel-type hook 11 is fixed to the axial center position of the upper part of the weight 3 by welding, and is formed into a structure of a suspension device 20 suspended from the ceiling by a suspension chain 21. When tightening, the weight load is applied to the sleeve thread, and tightened at 5 to 20 rpm until the torque rises. The initial temporary tightening position and the high-speed rotation of tightening / loosening form a loose simulation. If the torque rises, the rotation speed is reduced to 0.5 to 2 rpm, and tightening is implemented to the tightening position.
[0376] As a simulation of the tightening and loosening test in the actual well, in particular, during the loosening, the load of the weight 3 may be applied, or the load of the weight 3 may not be applied. During the loosening, it is preferred not to apply the load of the weight 3. In the following embodiment, during the loosening, the load of the weight 3 is not applied. If the loosening is carried out in the state of applying the load, when loosening from the tightening completion position, the weight becomes a "weight" and a balancer, and is loosened in a manner that the pin thread rises straightly. Therefore, the pin will not loosen, and during the loosening, the solid lubricating film will not be damaged. Even under the condition that the load is not zero, the load is hoisted for testing. Including the case where the load is not completely zero, under the condition that the load is relaxed, the test can be carried out under the condition that the loosening is severe and the tendency to damage the solid lubricating film is strong. Regarding the rotation speed during the loosening, when the torque rises, the rotation speed is set to 0.5 to 2 rpm to start loosening, and if the torque reaches about 1 / 10 of the tightening torque value, it is loosened at a high speed of 5 to 20 rpm. In this example, the evaluation was performed by the following method: when loosening was completed, the pin thread and the sleeve thread were separated from each other by loosening, and fragments from the solid lubricating film were scattered on each surface by air blowing, and the surface was inspected, and tightening was continued again.
[0377] The lubrication evaluation was performed using the following method and criteria.
[0378] According to the provisions of ISO13679, for the sleeve size, more than 3 times of tightening and loosening are judged as qualified, and for the pipe size, more than 10 times of tightening and loosening are judged as qualified. However, when considering the lubrication using a solid lubricating film, there is a tendency for the M / B times to deteriorate compared with the previous lubrication using a grease-like compound. The reasons for this are as follows. In the previous method using a grease-like compound, the grease-like compound attached to the surface is rinsed with an organic solvent each time the tightening and loosening is performed, and after the surface is inspected, the grease-like compound is reapplied. That is, it means that the main body of lubrication is supplied again. On the other hand, in the lubrication using a solid lubricating film, the thread surface is cleaned by blowing air, etc., but in particular, no lubricating component is added in the middle. As a result, the tendency of the tightening and loosening times to decrease using a solid lubricating film cannot be denied in any way.
[0379] Therefore, as a reference for the number of tightening and loosening in the present invention, for the sleeve size, more than 3 times of tightening and loosening are judged as acceptable. For the pipe size, more than 5 times of tightening and loosening are judged as acceptable. In addition, the sleeve size is set to be 7" or more, and for the pipe, it is divided into less than 7" for judgment. In addition to the M / B number, after loosening, if it is completely loosened, the pin is disengaged to the upper part, and the pin thread surface and the sleeve thread surface are observed after blowing, and the presence of burns is directly visually confirmed. In addition, the torque rotation diagram is checked to confirm whether there are abnormal points.
[0380] The NG judgment is made as follows. If the thread does not loosen during the M / B times of tightening and loosening, it is judged that a burn has occurred at the number of tightening and loosening, and the number of tightening and loosening is judged to be the previous number. In the case where the surface is completely loosened and can be observed, if a slight burn occurs in the sealing part, a judgment of NG is made on the spot. Then, the number of tightening and loosening is judged as the burn occurring at the next number, and the tightening test using the heavy hammer pliers is ended on the spot. In the case of very slight burns on the threaded part, repairs are performed and the test is continued directly. The number of tightening and loosening implemented in this way is used to screen the good and the bad according to the above-mentioned judgment criteria.
[0381] Example
[0382] Hereinafter, examples of the present invention will be described.
[0383] (Example 1: Method for preparing and uniformly mixing metal soap)
[0384] In the research group of this Example 1, the conditions for the mixing method of the metal soap were screened by mixing in a liquid. The mixing conditions of the metal soap were investigated using reagents with the following mixing ratios.
[0385] The solvent used was a mixture of water as the main component and industrial ethanol and ammonia water. As a solid lubricant, Ca stearate (metal soap: particle size 8 to 10 μm or less) and Na stearate (alkaline soap) were mixed in a weight ratio of 99:1. As a binder resin, a copolymer of vinyl acetate and methacrylic acid as monomers was used, which was prepared by mixing 10 parts by weight of methacrylic acid with 100 parts by weight of vinyl acetate. It should be noted that the copolymer described here corresponds to 100% of the "polymer having an acrylate or methacrylate structure" described in the present invention.
[0386] The respective mixing ratios were prepared so that the solvent (water) (measured by volume and converted to weight with a specific gravity of 1) was 3 times the total weight of the solid lubricant (metal soap + alkaline soap) and the binder resin. The mixing weight ratio of the solid lubricant was 0.1 times the weight of the binder resin.
[0387] When preparing these, a mixture of monomers for making a copolymer of vinyl acetate and methacrylic acid is prepared by mixing them in water. As shown below, a metal soap is prepared with industrial ethanol, and ammonia water is further added to adjust the pH to 7 to 8. On this basis, sodium stearate is finally prepared and mixed. A method of mixing a metal soap in this base reagent was studied.
[0388] <Condition 1>
[0389] Condition 1 is an example in which Ca stearate is directly added to the base reagent according to the above-mentioned mixing ratio and stirred. Condition 1 is an example in which industrial ethanol is not used at all.
[0390] In condition 1, the metal soap was not fully mixed, and the metal soap floated on the surface and aggregated with each other. That is, it was not well mixed uniformly. The results confirmed the conventional knowledge that metal soap is insoluble in water.
[0391] <Condition 2>
[0392] In condition 2, calcium stearate was added to the basic reagent according to the above mixing ratio and stirred. Then, industrial ethanol was added to water at a volume / volume ratio of 100:20.
[0393] In condition 2, the mixture was not mixed sufficiently, and the mixture floated on the surface and aggregated with each other. That is, the mixture could not be mixed well and homogeneously. Condition 2 showed that the metal soap could not be mixed well even if ethanol was added later.
[0394] <Condition 3>
[0395] Condition 3 is an example in which Ca stearate is stirred in industrial ethanol in an amount of 20 parts per 100 parts of water in another container, that is, mixed uniformly, and then the base reagent is added and stirred.
[0396] Condition 3 can be said to be an example of roughly homogeneous mixing. It is said that it is insoluble in both water and alcohol, but in alcohol (ethanol), it was confirmed that the particles of Ca stearate do not associate and agglomerate with each other, and a fine dispersion can be achieved. Therefore, it can be seen that by temporarily dissolving in ethanol (alcohol), spreading this state in the base reagent and stirring, a homogeneous dissolution of the metal soap can be achieved.
[0397] <Condition 4>
[0398] Condition 4 is an example in which Ca stearate is thoroughly stirred in industrial ethanol in an amount of 1:100 of water in another container and then added to the base reagent. Condition 4 is an example in which industrial ethanol is subsequently added in an amount of 1:19 to the base reagent and stirred.
[0399] In condition 4, when a small amount of ethanol was added to make the metal soap Ca stearate turbid, the metal soap was not fully mixed and floated on the surface, and was associated with each other to form lumps. That is, although it is an example of mixing it with the base reagent, it is equivalent to an example in which it is not well mixed homogeneously.
[0400] <Condition 5>
[0401] Condition 5 is an example in which Ca stearate is thoroughly stirred in industrial ethanol in an amount of 15:100 of water in another container and then added to the base reagent. Condition 5 is an example in which industrial ethanol is subsequently added to the base reagent in an amount of 5:10 and stirred.
[0402] In the system of condition 5, the metal soap Ca stearate is already homogeneously mixed in the industrial ethanol: 15. Therefore, it can be said that even if industrial ethanol is further added from this state, it can be said that it is an example in which it is mixed almost homogeneously.
[0403] The following can be understood from the examples of conditions 1 to 5. That is, a material in which an appropriate amount of metal soap or less is uniformly dissolved in an appropriate amount of an appropriate lower alcohol, that is, an amount that can fully mix the metal soap, is temporarily prepared, and is placed in the reagent body and stirred. In this case, the metal soap can be mixed into the solvent mainly composed of water. In addition, it can be seen that in the case of a metal soap in an amount that cannot be uniformly mixed based on the volume of the lower alcohol, there is a high tendency that it will not mix even if additional industrial ethanol is added after it is added to the base reagent.
[0404] In addition, in the following examples, the examples are further shown on the premise that the reagents in which the metal soap is uniformly mixed.
[0405] (Example 2: Early Drying, Coating Amount and Drying Method)
[0406] The research group of Example 2 applied the reagent to the structure of the oil well pipe thread and screened the good and bad according to the drying condition. The mixing ratio of alcohol and ammonia water, the different types of alcohol, and the size of the metal soap were studied. The reagents with the following reagent conditions changed were systematically prepared and the early drying properties were investigated.
[0407] The solvent is composed of alcohol and ammonia water relative to 100 parts of water as a solvent, and the solid lubricant is composed of metal soap and alkaline soap. As the binder resin, a copolymer prepared by mixing 6 parts by weight of polyvinyl alcohol as a monomer with 100 parts by weight of acrylic acid is used. For example, polyvinyl alcohol is Poval, which is obtained by saponifying polyvinyl acetate obtained by polymerizing vinyl acetate monomer.
[0408] The respective mixing ratios correspond to the contents of this study. In addition, in the solvent system, when the solvent (water) is set to 100 (measured by volume, converted to weight with a specific gravity of 1), conditions for changing the mixing conditions were prepared for industrial ethanol and ammonia water.
[0409] In addition, samples were prepared with different weights of the total weight of the solid lubricant (metal soap + alkaline soap) and the binder resin and the solvent, and the weight ratio of the metal soap and alkaline soap in the solid lubricating film. Furthermore, samples were prepared with different sizes of the metal soap. Then, the drying conditions were observed.
[0410] The preparation method is to mix sodium stearate before the last one. Finally, in order to adjust the pH to 6.5-8.5, ammonia water (about 28%) is mixed in the end.
[0411] The method identified by the research group in Example 1 above, that is, the method of mixing the metal soap in advance into the "lower alcohol (ethanol: Example 1)" and then mixing it in. The industrial ethanol mentioned here is high-purity ethanol. However, it means that methanol and isopropanol are mixed at a level that does not involve the liquor tax law.
[0412] As common experimental conditions, for oil well pipe threads, we prepared carbon steel, L80 grade, 5.5” 23#, and JFEBEAR thread. TM The pin thread is a short strip of 700-1000mm in length with oil well pipe threads processed at both ends. Regarding the method of applying the reagent, first, immerse the reagent in the bristles of a general paint brush (Japanese standard of bristles: No. 20: 50mm wide). Then, place the short pin on two rollers that rotate the same number of times and apply the reagent while rotating it at a speed of about 10 seconds to about 20 seconds per circle (refer to Figure 8). The two rollers are two axially rotating rollers that touch the 5.5" 23# pin thread at approximately the 5 o'clock and 7 o'clock positions. In addition, the bristles 30 are applied in the length direction of the tube 31 in a manner that the bristles 30 touch the thread rotation perpendicularly and only sweep 1 degree in one direction, so as not to repeat the coating of the same part of the thread at the same position of the bristles. The coated parts are the entire area of the thread, the end face of the front end of the pin thread, about 10 mm to the inside, and the area without thread teeth of about 30 mm to about 50 mm where the thread teeth are cut off (round head part). Both ends are evaluated as a group. It should be noted that about 10 mm on the inside is inevitably coated due to the winding of the bristles. The area without thread teeth of about 30 mm to about 50 mm is inevitably coated due to the winding of the bristles.
[0413] First, as an example of drying in the atmosphere, apply one side and leave it. Next, as an example of drying in the atmosphere, apply the other side while rotating in the same way, and continue rotating while drying with the smaller of the two-stage air volume switching in the atmospheric air supply mode of the manual dryer, for example, 1 m / sec. Then record the drying time. Then, stop the rotation of the tube and also record the drying time of the static drying side. Touch it with your hand, and judge it as dry if there are no fingerprints left and it is not sticky.
[0414] The position for judging the drying is judged by the drying of the 8 o'clock to 4 o'clock position on the upper side of the tube. In addition, the same judgment position is set on the side where it is left to dry. In the case of large-scale coating, the coating liquid accumulates at the 6 o'clock position, which is the static position. However, since the area other than the outermost surface has already solidified, it is judged that there is no problem with the drying of the coating, which is used as the basis for this judgment.
[0415] For static drying, if it cannot be considered dry within 30 minutes, it is recorded as more than 30 minutes. In addition, the indoor temperature on that day was 25-28°C, which was roughly the same temperature during drying. Setting the forced drying condition as a simple air supply condition is a slightly stricter condition that dries slower than the hot air blowing condition. However, if it is OK under this drying condition, it can be judged as qualified under any forced drying condition, so it is a study under the most stringent conditions conceivable.
[0416] The coating weight is calculated from the weight difference of the brush hairs. However, since it is a reagent with low viscosity and high fluidity, it is felt that semi-dried paint is accumulated at the 6 o'clock position, especially on the side that was placed after coating. Finally, there is also a part that drips from the 6 o'clock position, but its amount is ignored, and the simple weight difference of the brush hairs before and after coating is used as the coating amount. In addition, with the exception, the viscosity of the liquid is about 850 mPa·second, and there is no significant change under all conditions. The exception refers to less than 850 mPa·second when the solvent mixing ratio is increased. The exceptions with low fluidity correspond to the following No. 2-10 to 2-14. The case of increasing the solvent mixing ratio refers to the case of using a reagent that is mixed more dilutely using an aqueous solvent, for example.
[0417] It should be noted that in the following examples, the film weight is described, but the film thickness is not discussed. There is only one example in which the film thickness was measured, and a cross-sectional microscope inspection of No. 2-5 was carried out. In the pin thread shape of the oil well pipe thread, the thread root is 20 to 50 μm, and the top portion is about 20 μm to about 40 μm. In addition, the stab tooth belly (the longitudinal wall portion of the thread that touches when tightening the thread) and the load tooth belly (the longitudinal wall portion of the thread that touches when loosening the thread) are 5 to 10 μm. Depending on the way the bristles touch, it is a practical situation that there are deviations in the joints of the bristle coating, for example. The joints of the bristle coating refer to unstable parts such as the timing of adding reagents to the bristles and coating again, or the timing of pressing the bristles strongly in order to squeeze the coating liquid out of the bristles when the discharge of the coating liquid becomes less. Therefore, in the study of this embodiment, the bristles are used for coating, and the tube itself is also rotated. Thus, the coating is intended to be uniform. However, sometimes the viscosity of the liquid itself is low, and the film is formed from the dry part, while the undried paint part is easy to accumulate paint due to rotation. That is, the movement of the thread root to the groove is also a cause of the film thickness difference. The characteristics are evaluated based on the film thickness difference of this level. However, regarding the evaluation of the drying itself, as long as the tube is rotated, there is a high tendency to dry evenly, so the judgment of the completion of drying is judged by the drying time at the place where the drying is slowest.
[0418] Tables 1 to 3 show the details.
[0419] These are research examples on drying time. In addition, the lubrication characteristics of oil well pipe threads represented by M / B times are not evaluated in Tables 1 to 3. " means outside the regulations." ” means outside the preferred range.
[0420] The evaluation judgment here was evaluated as Invention Example (drying OK) / Invention Example (△: drying time was out of the preferred range) / Comparative Example.
[0421] The drying time of the example of the present invention (drying OK) was within the appropriate range specified in claims 10 and 11 of the present application, and satisfied the ranges shown in claims 1 to 9.
[0422] The example of the present invention (△: drying time is out of the preferred range) is an example that includes conditions that are NG from the perspective of drying time. That is, it is out of the preferred range. However, it is within the scope of the invention specified in the present invention. However, the tightening and loosening test is not shown.
[0423] For the comparative examples, the results were NG from the perspective of drying time, or the solid film was poorly formed, and it was not expected that the M / B number would be qualified. Therefore, the results were NG due to the difficulty of the tightening and loosening test itself. Furthermore, it means that the results are out of the scope of the invention specified in the present invention.
[0424]
[0425]
[0426]
[0427] No. 2-1 to No. 2-3 are examples in which alkaline soap is not added, and No. 2-1 is also an example in which alcohol and ammonia water are not added to the solvent.
[0428] In No.2-1, the drying state of the binder resin (copolymer of acrylic acid and vinyl alcohol) studied in the example was investigated in a state slightly exceeding the limit of thick coating. This is the drying characteristic of the combined binder resin. This is equivalent to the comparative example. Specifically, the solvent is only water, and does not contain alcohol, ammonia water, etc. Since it is only water, the Ca stearate characterized by water repellency is sometimes evenly dispersed and not dissolved in the reagent stage. Therefore, even in the state of forming a solid film, a large amount of Ca stearate components will not enter the film, but will be in a state of being carried on the film, which cannot be said to be good as a solid lubricating film. In addition, in the case where the drying time also becomes longer, it becomes the positioning of the comparative example.
[0429] In both No.2-2 and No.2-3, the volume ratio (volume / volume) of ethanol to water is 6. The former is an example without ammonia water, and the latter is an example with ammonia water mixed at a ratio of 0.5. The coating amount is within the target range, and both air drying and drying by placing meet the target values. That is, it is equivalent to the present invention example (drying OK). The drying time of No.2-3 is slightly shorter and improved. Due to the influence of the ammonia water, it is possible that the volatility is more or less well shifted.
[0430] No.2-4 is an example in which a small amount of alkaline soap component is added to No.2-3. Metal soap (Ca stearate) and alkaline soap (Na stearate) are added at a weight ratio of 99:1. The drying time is not inferior to No.2-3, and it is an example of the present invention.
[0431] No. 2-5 is an example in which methylamine, a primary amine, is added to the ammonia water of No. 2-4. It has the same level of drying performance as No. 2-4 and is an example of the present invention.
[0432] No. 2-4 and No. 2-6 to 2-9 are examples in which the ratio of industrial ethanol to water volume 100 is increased to 6, 10, 25, 25, and 43, respectively. These examples correspond to examples in which ammonia is 0.5, 1.0, 1.0, no addition, and 2.0, respectively.
[0433] In short, in the order of No. 2-4, 2-5, 2-7 and 2-8, 2-9, the drying time becomes shorter in turn, whether it is air drying or standing drying. This example shows that the more industrial ethanol is used, the faster the drying. They are all examples of the present invention (drying OK).
[0434] The case of No. 2-7 shows that even without ammonia, drying can be enhanced by the volatility of industrial ethanol alone. The cases of No. 2-4, 2-5, 2-6, and 2-8 can be interpreted as ammonia having a good effect on early drying.
[0435] In addition, in case No. 2-9, the total volume of alcohol and ammonia water relative to the volume of water was 45, which means that there was no problem in drying within this range.
[0436] Cases No. 2-10 to 2-15 are the results of studying the weight ratio of the solvent to the solid component (weight of the solid lubricant component + total weight of the binder resin). It should be noted that the weight of the solvent refers to the value converted into weight change by assuming a specific gravity of 1 and converting the volume of the solvent composed of water, alcohol and ammonia.
[0437] No.2-10 to No.2-11 are research cases where the industrial ethanol is 25 with respect to the water volume of 100. No.2 to 12 to 15 are research cases where the industrial ethanol is 40. Regarding the weight ratio of the solvent to the solid content, the former group is 0.7 and 30, respectively. The latter group is 20, 50, 100, and 130, respectively.
[0438] When the weight ratio of the solvent to the solid content reaches 100, the drying time targeted by the present invention can be met, which corresponds to the present invention examples (drying OK) (No. 2-11 to 2-14). On the other hand, in the case No. 2-15 where the weight ratio exceeds 100 and is 130, the drying time cannot meet the target by leaving it to dry, which becomes the present invention example (△: the drying time is out of the preferred range). The criterion for the drying time cannot be met, but it means that the basic structure of the present invention is met. However, the lubrication behavior is not described in Example 2.
[0439] No. 2-16 to 2-20 are the results of the study when the alkaline soap component was increased. It is also a case where the solvent was slightly increased (the weight ratio of the solvent was 2.5), and it is also an example where the alcohol content was high. It is an example where the weight ratio of the metal soap to the alkaline soap was 99:1, 99:1, 95:5, 90:10, and 80:20, respectively. Furthermore, the examples of No. 2-16 and 2-17 also have different coating amounts, the former is 6g, and the latter is 12g, and the latter's coating amount also slightly exceeds the target value of 0.1g / mm 2 example.
[0440] No.2-16 and 2-17 meet the criteria for air drying. However, in the case of standing drying, the former meets the criteria, while the latter does not. Sometimes the coating amount of the latter is twice that of the former, which is estimated to exceed the drying time criteria. If the coating amount exceeds the specified value: 0.1g / mm 2 , it is suggested that the preferred range of drying time may not be met, especially in the case of drying. The former is equivalent to the present invention example (drying OK), and the latter is equivalent to the present invention example (△: drying time is out of the preferred range). This is because if the preferred drying time is removed, the range specified in this application is met.
[0441] No. 2-18 is an example of the upper limit of the content of the alkaline soap. Compared with No. 2-15, the drying time is longer, but the target can be met. It is equivalent to the example of the present invention (drying is OK).
[0442] On the other hand, No. 2-19 and 2-20 exceeded the target, and the alkaline soap component (Na stearate) was too much, the viscosity of the solvent increased, and it was difficult to apply evenly. Moreover, even if applied, it took too long to dry, and the target value could not be met. Therefore, it is shown that adding too much alkaline soap is not good. In particular, No. 2-20 is an example in which the drying time exceeds the benchmark of the preferred range and becomes longer, and the viscosity increases excessively, and it cannot be applied evenly and is difficult to apply. No. 2-20 has uneven, dripping and very slow drying, and the accurate drying time cannot be found. Therefore, No. 2-19 and 2-20 are equivalent to comparative examples.
[0443] Case Nos. 2-21 to 2-26 are a series of studies on lower alcohols.
[0444] No.2-21 corresponds to the research case of methanol, Nos.2-22 to 2-24 correspond to the research case of isopropanol, No.2-25 corresponds to the research case of n-propanol, and No.2-26 corresponds to the research case of isobutanol.
[0445] Nos. 2-22 to 2-24 are results of investigating the influence of the film thickness of the solid lubricating film (solid lubricating film).
[0446] No. 2-21 to 2-25 are examples with carbon atoms of 3 or less. When methanol, ethanol (examples of No. 2-2 to 2-20), isopropanol, and n-propanol are used, the metal soap content is the specified amount. It is also shown that if the target film thickness of 0.1 g / mm is met, 2 Below, the drying target can be satisfied. No. 2-21 to 2-23 and No. 2-25 correspond to the examples of the present invention (drying OK).
[0447] On the other hand, No. 2-24 is an example in which isopropyl alcohol was used and the film thickness exceeded the target value, which is an example that does not meet the target value of the preferred range of drying time. Since the basic structure of the present invention is met (experimental data omitted), it is equivalent to the present invention example (△: drying time is out of the preferred range).
[0448] No.2-26 is an example of isobutanol with 4 carbon atoms. As a problem before coating, the metal soap was not well mixed into the aqueous solvent when the reagent was prepared, so it was used as a comparative example. If the number of carbon atoms increases, the solid solubility with water gradually deteriorates. Therefore, even if the metal soap can be uniformly dispersed and dissolved in isobutanol, when they are spread in water to form a mixed state, when it is considered as a coating, it can also be described as follows. That is, it is presumed that the substance formed by the dissolution of isobutanol and the metal soap is not well mixed into the solvent of the water main body. Therefore, before discussing the drying time, a uniform coating film is not formed, so it is positioned as a comparative example.
[0449] Examples No. 2-27 to 2-33 are the results of investigating the effects of the types of metal soaps and alkaline soaps and the particle size of the metal soaps. Examples No. 2-27 to 2-29 are examples of Ca stearate and Na stearate. Example No. 2-30 is an example of Zn stearate and Na oleate. Example No. 2-31 is an example of Mg stearate and K stearate. Example No. 2-32 is an example of Ca montanate and Na 12-hydroxystearate, and Example No. 2-33 is an example of Ca behenate and Na laurate. Furthermore, the effects of fine particles of metal soaps were investigated.
[0450] As shown in Example No. 2-29, when the particle size of the metal soap is 25 μm, the drying time exceeds the prescribed range and becomes longer. However, in the case of a particle size of 10 μm or less in other examples, the prescribed range of the preferred drying time is met, and early drying can be performed. That is, it can be seen that although there is a tendency for drying to be intensified when a metal soap is added, there is a tendency to meet the target drying time by making the particle size 10 μm or less. In addition, it can be seen that the types of metal soap and alkaline soap can be applied without particular problems within the scope of the present invention.
[0451] No. 2-29 can be determined as an example of the present invention (△: drying time is out of the preferred range), and Nos. 2-27 to 2-34 correspond to examples of the present invention (drying OK).
[0452] The reason why No. 2-29 corresponds to the example of the present invention (△: drying time is out of the preferred range) is as follows. That is, the metal soap (Ca stearate) is 25 μm, and as mentioned above, the film thickness of the vertical wall portion, stab flank, and load flank of the oil well pipe thread mostly has a region smaller than the particle size of the metal soap. Therefore, it can be assumed that the integrity of the film cannot be always maintained during lubrication, and the long-term rust prevention performance may cause problems.
[0453] (Example 3: Effect of various conditions on lubricity)
[0454] The research group of Example 3 applied a reagent to the structure of the oil well pipe thread to form a film, and investigated the lubrication behavior using a heavy hammer clamp test to illustrate the invention.
[0455] The weight is applied when tightening. On the other hand, in order to make the weight load close to zero when loosening, Figure 5 The bridge crane 20 was lifted to simulate looseness. A combination of various conditions was systematically prepared for research, and the feasibility was determined based on the lubrication behavior, that is, the M / B number.
[0456] Reflecting the contents of the study in Example 1, the metal soap component is dispersed and uniformly dissolved in a lower alcohol in advance, and is uniformly dispersed to prepare a reagent.
[0457] As for the judgment criteria of lubrication characteristics using a heavy hammer pliers, as described above, for the casing size, tightening and loosening more than 3 times is judged as acceptable. For the pipe size, tightening and loosening more than 5 times is judged as acceptable. In addition, the casing size is set to be 7" or more, and for the pipe, it is judged to be less than 7". In thread test standards such as API-5C5, the material equivalent to the pipe is based on whether it reaches more than 10 M / B times in the previous lubrication requirements with API-mod compounds. However, for solid lubricating films, it is inevitable that the film itself is gradually ground, so there is a tendency for the number to decrease. Therefore, in this application, more than 5 times are set as the acceptable range.
[0458] Except for the M / B times, after loosening, loosen completely and withdraw the pin upward. Then, observe the pin thread surface and the sleeve thread surface after blowing, and directly visually check whether there is any burning. In addition, check the torque rotation diagram to confirm whether there is any abnormal point. The judgment method is as follows. During the tightening and loosening process of the M / B times, if the thread does not loosen, it is judged that burning has occurred at the number of tightening and loosening, and the tightening and loosening times are judged as the previous number.
[0459] In the case where the surface can be observed after the complete loosening, if the seal part is burned even if it is slightly burned, it is judged as NG. Then, the number of tightening and loosening is judged as the number of times that burning occurs at the next time, and the number of tightening with a heavy hammer pliers is recorded on the spot to complete the tightening and loosening test. In the case of very slight burning not in the seal part but in the thread part, repair it and continue the test directly. Through the number of tightening and loosening implemented in this way, the quality is selected according to the above judgment criteria.
[0460] The conditions and results are shown in Tables 4 to 12. The symbols in the parameters in the tables are " " means outside the regulations. The symbol " ” means outside the preferred range.
[0461]
[0462]
[0463]
[0464]
[0465]
[0466]
[0467]
[0468]
[0469]
[0470] In the table, the "Solid Lubricating Film A with Pencil Hardness 3H" that appears in large quantities is as follows. That is, in the case of carbon steel, a solid lubricating film is formed on the basis of a base layer of a Mn phosphate chemical conversion treatment film and a stainless steel material. In this case, it can be regarded as a solid lubricating film composed of a binder resin: polyamide-imide film, a solid lubricant: PTFE and a trace amount of MoS 2 (1-3%) is a structure in which the solid lubricating film is roughly evenly dispersed. Moreover, it means that the film thickness of the solid lubricating film is 50μm-80μm. The film thickness is set as the measured value of the film thickness of the thread. Including the pencil hardness of 3H, it refers to a common and identical solid lubricating film. It should be noted that the distribution of the film thickness of each part of the thread is as follows. That is, the thread design of the oil well pipe thread adopts a barb-type structure. Therefore, although a method is used to apply the reagent with the goal of uniform film thickness, the thread teeth of the load tooth belly and the stab tooth belly cannot avoid the tendency of the film thickness of the longitudinal wall part to decrease. However, by studying the film formation of the solid lubricating film, a film is formed in a way that can ensure a film thickness of more than half of the measured value of the film thickness of the thread teeth in the longitudinal wall part.
[0471] In No.3-1 to 3-12, for material grade, carbon steel: P110 material, 7” 38# JFELION TM The thread, as a reagent, is a copolymer of styrene-acrylic acid (when the acrylic acid ester is set to 100 parts by weight, the styrene is 500 parts by weight). And, this is an example of forming it on the pin thread side. In addition, the sleeve thread side is a condition where the above-mentioned "solid lubricating film A with a pencil hardness of 3H" is formed. In this case, a Mn phosphate chemical conversion treatment film is formed on the substrate. A tightening and loosening test using a 2-ton weight equivalent to the tightening when three threads are connected is carried out to determine whether it is possible.
[0472] In the cases of No.3-1 to 3-8, the solvent is composed of 15 industrial ethanol and 2 ammonia water in a ratio relative to 100 volume of water. Their mixing ratios are also common, and they are mixed under the same conditions within the specified range. These are research examples with different conditions for the size of the metal soap, the presence or absence of alkaline soap, and the film thickness. No.3-1 to 3-4 are examples in which the particle sizes of the metal soap (Ca stearate) are 5μm, 1μm, 10μm (only this example does not contain alkaline soap), and 10μm, respectively. No.3-1, 2, and 4 show good lubrication behavior when the number of M / B using a heavy hammer clamp is more than 10 times (stopped at 10 times), which is equivalent to the examples of the present invention. The number of M / B of No.3-3 stops at 3 times, which is equivalent to the examples of the present invention. However, compared with No.3-1, 2, and 4 containing alkaline soap components, the lubrication properties of No.3-3 are deteriorated. It shows that the addition of alkaline soap is effective in improving lubrication.
[0473] The size of the metal soap in No. 3-5 to 3-8 is 25 μm. However, the film thickness of the solid lubricating film is 20 μm, 50 μm, 100 μm, and 180 μm, respectively. In addition, these examples are examples in which the drying time is 7 minutes of air drying, 23 minutes of air drying, 8 minutes of hot air drying, and 10 minutes of hot air drying, respectively. No. 3-7 and 3-8 are dried using a hot air blower (output power 1000 W).
[0474] In short, there is a tendency to become longer compared to No. 3-1 to 3-4. This change is considered to be affected by the increase in the size of the solid lubricating film and the particle size of the metal soap. When the particle size of the metal soap is small and dispersed, the surface area increases, and the drying points in the film increase. As a result, it can be expected that drying will be accelerated. However, in these cases, this can be explained by the fact that this situation cannot be expected when the size is large, and the volume required for drying increases due to the influence of the film thickness.
[0475] No.3-5 is an example of a film thickness of 20 μm, which is an example in which the size of the metal soap is relatively large relative to the film thickness. They are examples in which when the metal soap is larger than the film thickness, there is a part where it is difficult to maintain the integrity of the film, and this part is destroyed and burns occur. The M / B times of No.3-6 (film thickness 50 μm) are 6 or 7 times, which is equivalent to the invention example. No.3-7 and 3-8 investigated the influence of film thickness. The former can meet the M / B times when the film thickness is 100 μm, but the latter sometimes has a situation in which the M / B times do not meet the benchmark of 3 times in some samples when the film thickness is 180 μm. That is to say, if the film thickness exceeds 100 μm, the lubrication performance sometimes deteriorates.
[0476] No.3-9 and 10 are comparative study cases in which the drying method was changed. They are explained by comparing them with No.3-1. The above-mentioned No.3-1 is a case in which the M / B frequency can be performed more than 10 times (stopped at 10 times). No.3-9 is the same as before, in which the tube is rotated while applying the brush once. However, in the case of directly rotating only the pin threaded tube and drying in the atmosphere, it is an example of drying for 15 minutes. In No.3-10, after the rotary coating, the rotation is stopped and the tube is left to stand for drying, which is an example in which additional drying time is spent.
[0477] It should be noted that, as described above, the judgment of drying is implemented on the upper side of the tube at the 8 o'clock to 4 o'clock positions. This judgment can be made because the lower part of the coating film is sometimes filmized, which can be inferred by the drying at the 8 o'clock to 4 o'clock positions. In addition, this is because, in this case, the 5 o'clock to 7 o'clock positions where there is liquid accumulation are also in a state where the surface is dry except for the lower part of the coating film but has not yet completely dried to the middle, so it can be considered that there is no problem with corrosion resistance. As shown in this example, the lubrication behavior is slightly worse than No. 3-1 and 3-9, but it is in the qualified range. The lubrication can be considered to be in an excellent range and can be considered as an example of the present invention. The reason is that the viscosity of the reagent is small and the fluidity is correspondingly high. The coating that is not completely dried at the end of coating is related to the fact that there is liquid moving along the thread (dripping). Although the positions of 5 o'clock to 7 o'clock are considered to be affected by the part that is dry on the surface but not completely dried to the middle, it is in the qualified range.
[0478] Examples No. 3-11 to 3-12 are examples of research on the case where the binder resin contains substances other than the binder resin components other than acrylates or methacrylates. These are examples in which 11 parts by weight and 35 parts by weight of water-soluble phenolic resin are respectively prepared when the binder resin components other than methacrylates are set to 100 parts by weight. The former is equivalent to the present invention example, and the latter is an example in which the mixture is prepared in excess of the upper limit of the standard, which is equivalent to the comparative example.
[0479] If the weight ratio of the binder resin other than acrylate or methacrylate in the total binder resin is expressed, the cases are 90% and 74% (※less than the standard 90%), respectively. The former is an invention example in which the M / B times meet the regulations. The former is an example in which the mixing ratio of solvent / (solid lubricant+binder resin) is 1.8, the weight ratio of solid lubricant / binder resin is 0.12, and the viscosity is 650mPa·second. The latter is an example in which the ratios are 1.8, 0.12, and 1300mPa·second, respectively.
[0480] On the other hand, the latter was coated with a solid lubricating film with a target thickness of 25 μm, but it was not completely dry. Moreover, it did not dry even after waiting overnight after coating, but remained in a semi-wet state, and the tightening and loosening test could not be performed, so it was determined to be a comparative example.
[0481] In case No.3-13 to 3-17, for material grade, carbon steel: Q125 material, 9-5 / 8” 53.5# JFELION TM The thread, as a reagent, is vinyl acetate-butyl acrylate, polyethylene polymer (420:100:75). This is an example of forming it on the external thread side. In addition, the sleeve thread side is a condition where the above-mentioned "solid lubricating film A with a pencil hardness of 3H" is formed. Moreover, a Mn phosphate chemical conversion treatment film is formed on the base of this condition. A tightening and loosening test using a 3-ton weight equivalent to the tightening when three roots are connected is implemented to determine whether it is feasible. This is an example of research on increasing the addition of lower alcohol (ethanol), increasing volatility, and strengthening drying.
[0482] The solvent ratio of industrial ethanol to water is 100, and the ratios are 35, 35, 35, 45, and 60, respectively. The coating method is spin coating / air drying, spin coating / air drying, static coating (manual coating) / static drying, spin coating / static drying, and static coating (manual coating) / static drying, respectively.
[0483] No.3-17, which only exceeds the upper limit of the standard by 45 and contains 60 low-grade alcohols, does not meet the standard for the number of tightening and loosening. If the tightening and loosening test is performed using a heavy hammer tongs, the M / B times are poor overall, although they are at a qualified level, such as 5 times, 1 time, and 2 times. Therefore, as a comparative example. This suggests that there is a situation where the uniformity of the film thickness cannot be achieved due to excessive early drying. In addition, if the flash point is assumed to be 40°C and the coating is performed at the well site, there is a risk of accidents such as explosions, so it can also be judged as unqualified at this point.
[0484] In other cases, the M / B times meet the qualified standard. The M / B times of No. 3-13 stopped at the lower limit of 3 times, which is estimated to be because the solid lubricant / binder resin exceeds the preferred range of 1.0. In the case of a solid lubricating film with a large amount of solid lubricant, it is speculated that the cause is slightly poor soundness of the film. In addition, according to the research examples of No. 3-15 to 17, the cases of manual coating and / or static drying (without air supply) tend to have slightly worse M / B times. It is assumed that it is caused by the uneven film thickness during drying, which is used to make the undried reagent gradually flow to the 6 o'clock position while forming a film.
[0485] In case No. 3-18 to 34, for material grade, martensitic stainless steel HP2-13CR-110 (13Cr-5Ni-2Mo system), size: 9-5 / 8” 43.5# JFELION TM The thread, as a reagent, is an ethylene-methacrylic acid copolymer resin. The ethylene here is based on a random copolymer of ethylene oxide and propylene oxide, and is an example of using polymerized ethylene-methacrylic acid to form the external thread side. The sleeve thread side is formed with a Cu-Sn binary electroplated indicator film on its base under the condition of forming a "solid lubricating film A with a pencil hardness of 3H". A tightening and loosening test using a 2-ton weight is implemented to determine whether it is possible, and the weight is applied under the condition of tightening equivalent to the connection of less than 3 roots in the actual well.
[0486] In Nos. 3-19 to 22 and 3-24 to 33, the number of tightening and loosening in the tightening and loosening test using a weight clamp is within the acceptable range, and they correspond to the examples of the present invention. Nos. 3-18, 23, and 34 correspond to comparative examples.
[0487] The cases of No.3-18 to 3-21 are examples of the lower limit of the content ratio of low-level alcohols. No.3-18 is an example of a pure water-only solvent without the addition of alcohol. Moreover, the drying was performed with warm air at 100°C, and in particular, there was no case where the drying time was significantly long. However, the tightening and loosening test using a heavy hammer pliers was judged as unqualified after only one time, which is the positioning of the comparative example. Since the solvent is only water, the metal soap, the main component of the solid lubricant, is water-repellent. This can also be considered to be related to the following: since it cannot be well uniformly dispersed, the film quality is not homogeneous even at the stage of becoming a solid lubricating film.
[0488] No. 3-19 to 21 are examples where the industrial ethanol values are 0.5, 1, and 5, respectively. From No. 3-19 (industrial ethanol: 0.5), it can be confirmed that the M / B frequency is within the acceptable range.
[0489] No.3-22 to No.24 are research cases when a third solid lubricant other than metal soap and alkaline soap is contained, and they are cases where graphite, graphite, and BN are added, respectively. The M / B times of No.3-22 and 24 adjusted within the specified range are within the qualified range, which is equivalent to the present invention example. No.3-23 is an example that contains a large amount of a third solid lubricant (graphite in this case), and the metal soap and alkaline soap are not less than the specified weight % relative to the total solid lubricant. In these cases, the M / B times do not meet the qualified criteria and are NG, which is equivalent to the comparative example. In fact, graphite forms a band-like product of more than 20 mm along the groove of the thread tooth, which becomes the cause of burning.
[0490] Examples No. 3-25 to 27 are examples of completely drying the solid lubricating film by changing the coating method and drying method using the same solvent, binder resin, and solid lubricant, and comparative study examples in which a semi-dried portion remains. No. 3-25 is an example in which the coating is performed by brush coating while rotating the tube, and then air drying is performed while rotating the tube. In the completely dried film, the M / B times using a weight clamp are acceptable, which is equivalent to the present invention example.
[0491] No.3-26, 27 and No.3-25 have the same process before coating, but the drying is different. They are examples of forming a solid lubricating film that is left to dry. No.3-26 is an example of complete drying, and No.3-27 is an example of a residual part that is felt to be insufficiently dried. To be precise, there is a part of the liquid coating that is not completely dried at the 5 o'clock to 7 o'clock position. In addition, the film formation (drying) of the coating proceeds from the outermost layer (the contact surface with the atmosphere) and the contact surface of the threaded steel material. Therefore, in this case, a semi-dried part remains near the middle of the film thickness. This is an example of drying the contact surface between the thread and the coating. Although the coating and drying times are set to the same, there are some deviations in the coating method, which is presumed to be affected by them, but there is no problem with lubrication, and they are all equivalent to the examples of the present invention.
[0492] The cases of No. 3-28 to 32 are examples of comparative study of the influence of the weight ratio of the solvent to the total weight of the solid lubricant and the binder resin (where the specific gravity of the solvent is set to 1 for calculation) and the weight ratio of the solid lubricant / binder resin. The parameters of the two were set to 100-0.6, 150△-5.0△, 0.7-0.1, 0.5▽-0.08▽, and 0.6▽-1.1△ for study. It should be noted that △: exceeds the upper limit of the preferred range, and ▽: is lower than the lower limit of the preferred range. All conditions are invention examples. Regarding the preferred range, the M / B number is shown to be 6 times in No. 3-28 and 10 times in No. 3-30, which is a good M / B number. However, when the preferred range is exceeded, the lubrication performance is only limited to about 3 or 4 times.
[0493] Examples No. 3-33 and 34 are examples in which other solvents are added to the solvent in addition to water and alcohol, and are examples in which DMSO (dimethyl sulfoxide) is added. In the former, 6 volumes of DMSO are added to a base reagent in which the volume of industrial ethanol is set to 14 when the volume of water is set to 100. Moreover, it is an example in which the volume of water and lower alcohols is 95% and other solvents are 5% relative to the total weight of the solvent, and it is an example of studying the limit value of the solvent composition of the present application. These examples are examples in which stable polar solvents that are difficult to evaporate are added, and if hot air drying is used, it can be dried in about 5 minutes. However, it is an example in which it does not dry within the prescribed 5 minutes under air drying in the normal temperature area, and it cannot be dried in 30 minutes even if it is left to dry. If it can be filmed, the lubrication level targeted by the present application can be met, and it is therefore equivalent to the present invention example.
[0494] On the other hand, No. 3-34 is an example of adding more DMSO, which is a solvent with a large amount of DMSO with a high boiling point (about 190°C). Therefore, it is not dried whether it is left in the air to dry or blown to dry (including hot air), and it cannot be filmed. This can be filmed in a heat treatment above 200°C. However, the viscosity of the formulated solvent is sometimes low, and it cannot be filmed instantly during the firing process, and dripping occurs during firing. Specifically, a thick film is formed at the 6 o'clock position, and the bottom of the pin thread can be seen everywhere. In some parts, there is a tendency for dripping to further form a droplet-shaped film. Therefore, even if the tightening and loosening test is carried out, the required number of times cannot be reached, and burns occur, so it is NG, which is equivalent to a comparative example. From these studies, it can be seen that the proportion of water and lower alcohols in the solvent needs to be more than 95%.
[0495] Case No.3-35~39 is as follows: Material grade: carbon steel T95, size: 5.5” 23# JFELION TM The thread is a reagent of diacetone acrylamide (DAAD: an acrylic ester) and a polymer of diphenylmethane diisocyanate (MDI: a carbamate compound), and 40 parts by weight of MDI is mixed when 100 parts by weight of DAAD of the acrylic ester is used. A Cu-Sn binary electroplating indicator film is formed on the base of the sleeve thread side under the condition of forming a "solid lubricating film A with a pencil hardness of 3H". A tightening and loosening test using a 1-ton weight is carried out to determine whether it is possible, and the weight is applied under the condition of tightening when less than 3 roots are connected in an actual well.
[0496] No.3-35 to 39 are examples of forming a solid lubricating film by changing the coating method and drying method. There are five examples, namely, rotary coating-rotary air drying, rotary coating-static drying, manual coating after static drying, rotary coating-rotary air drying, and rotary coating-rotary air drying. The M / B times of the heavy hammer are ≥10 times (stop at 10 times), ≥10 times (stop at 10 times), 9 times, 8 times, and 9 times, respectively. All are qualified, which is equivalent to the examples of the present invention. Compared with the examples of No.3-1 to 3-34, the tightening torque becomes smaller because it is a small-diameter material, so it shows that whether it is based on manual coating after static or based on static drying, it does not have much effect on the uneven distribution of film thickness.
[0497] Examples No. 3-38 and 39 are examples in which metal soaps of other types were used than Ca stearate and Ca / Zn stearate (mixed) used in Examples No. 3-1 to 3-37. The former is an example in which Zn stearate was used, and the latter is an example in which Ba stearate was used. Both are examples in which other requirements fall within the prescribed range, and the M / B times are within the acceptable range, and are examples of the present invention.
[0498] The case No.3-40~43 is for JFEBEAR with material grade: carbon steel T95, size: 3.5” 9.2# TM This is an example of using a copolymer of acrylic acid and polyvinyl acetate as a reagent for threads. It is also an example of mixing a reagent of polyvinyl acetate with 30 parts by weight when the acrylic acid is set to 100 parts by weight. In this example, as a condition for using "solid lubricating film A with a pencil hardness of 3H" for sleeve threads, there is a Mn phosphate chemical conversion treatment film on the base. In addition, there are examples for pin threads, examples in which only two thread surfaces are formed by reagents, and research examples that only include Mn phosphate chemical conversion treatment films. A tightening and loosening test is performed by applying a 500kg weight to determine whether it is feasible, which is equivalent to applying a weight equivalent to the tightening of three connections in an actual well.
[0499] No.3-40 is the same as the above series of examples, and has a solid lubricating film on the pin thread side, and a "solid lubricating film A with a pencil hardness of 3H" is formed on the sleeve thread side. In addition, it is an example of the present invention in which the M / B number can be ≥10 times (stopped at 10 times). No.3-41 is an example in which a solid lubricating film is provided on the pin thread side, and the sleeve thread is only a Mn phosphate film without a "solid lubricating film A with a pencil hardness of 3H", but it can be tightened and loosened three times, which is equivalent to the example of the present invention.
[0500] No.3-42 is an example in which both sides of the thread are the solid lubricating film of the present invention, and 5 tightening and loosening can be confirmed, which is also equivalent to the invention example. No.3-43 is an example in which the sleeve thread is a solid lubricating film and the pin thread side is provided with a "solid lubricating film A with a pencil hardness of 3H", and the M / B number can be ≥10 times (stopped at 10 times), which is also equivalent to the invention example.
[0501] (Example 4) Results of studies on corrosion
[0502] The results are shown in Table 13.
[0503] [Table 13]
[0504]
[0505] In the corrosion resistance evaluation of the present invention, for a steel pipe having a thread structure such as an oil well pipe thread, the protective device for protecting the thread structure is temporarily tightened and then loosened, and then the solid lubricating film is sprayed with salt water with the protective device removed. In addition, the sample with red rust on the entire surface is judged as NG. The evaluation is performed by temporarily applying conceivable damage to the film and then using salt water spray. The corrosion resistance is studied using part of the materials and conditions studied in Tables 1 to 12.
[0506] It should be noted that the conditions for salt spray were determined by the method according to JIS K 5600-7-1 under 5% NaCl neutral salt spray conditions (35°C, humidity 98-99%, spray 1-2 mL / Hr / 80 cm 2 , pH 6.5-7.2), based on 8 hours of evaluation.
[0507] Here, the metal surface (threaded surface of oil well pipe) of the metal part that is the object of the present invention includes, for example, the surface after lathe processing, cutting processing, and the surface of the ground surface. In addition, as a corrosion resistance evaluation, the portion where the rolling oxide scale remains is removed. Depending on the roundness and eccentricity of the tubular structure, there may be a sample that contains rolling oxide scale in the thread structure. However, with regard to the rolling oxide scale, when cleaning is performed before forming a solid lubricating film, the aqueous reagent enters the tiny defects, holes, and damage of the rolling oxide scale. Therefore, when a solid lubricating film is formed thereon, even if the solid lubricating film is sound, pitting rust may sometimes be generated from the steel of the base. However, this pitting rust is not rust of the solid lubricating film, and is therefore excluded from the evaluation.
[0508] Sample No. in Table 13 refers to the reagent composition based on the components and structures used in Tables 1 to 12. The coating method is different from that of Sample No., and the coating is carried out with a brush while the tube is rotating. The drying method is rotating and air drying, which is an example of complete drying. In addition, all materials are mixed with L80, 3.5" 9.2# JFELION TM The case of studying the consistency of the PIN thread (external thread) of the steel sheet. After completely drying, the protective device made of HDPE resin (high-density polyethylene) was tightened / loosened once and the salt spray test was performed. As a comparative material, the SPCC material with a general-purpose thin steel plate was prepared and the material obtained by applying the reagents No. 3-1, 13, 17, 20, 38, and 42 to the pin thread was tested. However, the SPCC of the comparative material was not coated with rust preventive oil, and the operation equivalent to the tightening / loosening of the protective device once was not performed.
[0509] The results showed that the materials coated with the reagent of the present application were all excellent in corrosion resistance.
[0510] (other)
[0511] The present invention may also take the following configurations.
[0512] (1) A reagent for forming a solid lubricating film on a metal surface, wherein:
[0513] With solid lubricant, binder resin and solvent as main components,
[0514] The solvent contains water as a main component, and a lower alcohol having a carbon number of 3 or less is added to the water as an additive, wherein the volume of the additive is 0.5 or more and 45 or less relative to 100 of the volume of the water in the solvent,
[0515] More than 95% of the volume of the solvent is composed of the water and the additives.
[0516] The solid lubricant comprises a soap component including at least a metal soap of a metal soap and an alkaline soap component, wherein the metal soap component accounts for 95% or more of the total weight of the metal soap and the alkaline soap component.
[0517] The particle size of the metal soap is such that it does not exceed the film thickness of the solid lubricating film.
[0518] The binder resin contains water-soluble or water-dispersible polymers and copolymers, and contains polymers and copolymers having an acrylate or methacrylate structure in an amount of more than 90% by weight of the total weight of the binder resin.
[0519] (2) The additive further contains at least one of aqueous ammonia and a primary amine.
[0520] (3) The lower alcohol comprises one or more lower alcohols selected from methanol, ethanol, isopropanol, n-propanol and industrial ethanol, and the volume of the lower alcohol is 0.5 or more relative to 100 of the volume of water in the solvent.
[0521] (4) The metal soap and alkaline soap components constituting the solid lubricant include one or more soaps, wherein the soap is a compound formed of a fatty acid selected from the following Group A and a metal element selected from the following Group B,
[0522] The weight of the metal soap is more than 95% of the total weight of the metal soap and the alkaline soap.
[0523] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid;
[0524] Group B: Na, K, Mg, Ca, Zn.
[0525] (5) The particle size of the metal soap is 10 μm or less.
[0526] (6) The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of one or more monomers selected from the following (1) to (4), and the copolymer is a copolymer containing two or more monomers selected from the following (1) to (4).
[0527] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0528] (2) monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters and their derivatives among acrylates, methacrylates and their derivatives;
[0529] (3) A monomer grafted with the above (1) or (2);
[0530] (4) A monomer of either or both of a vinyl compound and a urethane compound.
[0531] (7) The flash point of the reagent exceeds 60°C or it is flame retardant.
[0532] (8) When the specific gravity of the solvent is set to 1 and the volume of the solvent is converted to weight,
[0533] The weight of the solvent is 0.7 times or more and 100 times or less of the total weight of the solid lubricant and the binder resin.
[0534] The weight of the solid lubricant is 0.1 times or more and 1.0 times or less the weight of the binder resin.
[0535] (9) The viscosity of the reagent is 1000 mPa·s or less.
[0536] (10) On the metal surface, 0.1g / mm 2 When the coating amount below is applied, it has an early drying property that allows the coating to dry within 30 minutes when left to dry in a windless atmosphere at normal temperature.
[0537] (11) On the metal surface, 0.1g / mm 2 When the coating amount below is applied, it has an early drying property that allows drying within 5 minutes when drying is performed in an air environment at room temperature with air blowing at 1 m / sec or more.
[0538] (12) The method for producing a solid lubricating film-forming agent of the present invention comprises preparing the metal soap by dispersing the metal soap in a lower alcohol to make it turbid and then adding the dispersed metal soap into water as a solvent.
[0539] (13) A method for applying the solid lubricating film-forming agent of the present invention onto the surface of a tubular member, wherein the agent is applied while the tubular member is axially rotating.
[0540] (14) An oil country pipe having a lubricating film having a solid lubricating film formed on a threaded portion, wherein:
[0541] In the above solid lubricating film, the solid lubricant is dispersed in the binder resin.
[0542] The solid lubricant contains a soap component including at least a metal soap of a metal soap and an alkaline soap component, wherein the metal soap component accounts for 95% or more of the total weight of the metal soap and the alkaline soap component.
[0543] The particle size of the metal soap is such that it does not exceed the film thickness of the solid lubricating film.
[0544] The binder resin contains water-soluble or water-dispersible polymers and copolymers, and contains polymers and copolymers having an acrylate or methacrylate structure in an amount of more than 90% by weight of the total weight of the binder resin.
[0545] (15) The metal soap and alkaline soap components constituting the solid lubricant include one or more soaps, wherein the soap is a compound formed of a fatty acid selected from the following Group A and a metal element selected from the following Group B,
[0546] The weight of the metal soap is 95% or more of the total weight of the metal soap and the alkaline soap.
[0547] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid;
[0548] Group B: Na, K, Mg, Ca, Zn.
[0549] (16) The particle size of the metal soap is 10 μm or less.
[0550] (17) The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of one or more monomers selected from the following (1) to (4), and the copolymer is a copolymer containing two or more monomers selected from the following (1) to (4),
[0551] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0552] (2) monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters and their derivatives among acrylates, methacrylates and their derivatives;
[0553] (3) A monomer grafted with the above (1) or (2);
[0554] (4) A monomer of either or both of a vinyl compound and a urethane compound.
[0555] (18) The solid lubricating film has a film thickness of 1 μm or more and 100 μm or less and is soft with a hardness of H or less in pencil hardness.
[0556] (19) A threaded joint for oil well pipes formed by connecting a sleeve having an internal thread and a pin having an external thread, wherein:
[0557] At least one of the sleeve and the pin is formed of an oil country tubular good having the solid lubricating film of the present invention formed thereon.
[0558] (20) A threaded joint for oil well pipes formed by connecting a sleeve having an internal thread and a pin having an external thread, wherein:
[0559] The oil country pipe of one of the sleeve and the pin is composed of the oil country pipe having the solid lubricating film of the present invention formed thereon,
[0560] A film having a higher hardness than the solid lubricating film is formed on the threaded portion of the other oil country tubular good.
[0561] The entire contents of Japanese Patent Application No. 2022-134375 (filed on August 25, 2022) to which this application claims priority are incorporated herein by reference. The invention is described herein with reference to a limited number of embodiments, but the scope of the invention is not limited thereto, and changes based on the above disclosed embodiments are obvious to those skilled in the art.
[0562] Explanation of symbols
[0563] 1 pin
[0564] 1a Threaded part
[0565] 2 sleeves
[0566] 2a Threaded part
Claims
1. A solid lubricating film-forming reagent, which is a reagent for forming a solid lubricating film on a metal surface, wherein: The reagent has a solid lubricant, a binder resin and a solvent as main components, The solvent contains water as a main component, and a lower alcohol having a carbon number of 3 or less is added to the water as an additive, wherein the volume of the additive is 0.5 or more and 45 or less relative to 100 of the volume of the water in the solvent, More than 95% of the volume of the solvent is composed of the water and the additive, The solid lubricant comprises a soap component including at least a metal soap of a metal soap and an alkaline soap component, wherein the metal soap component accounts for 95% or more of the total weight of the metal soap and the alkaline soap component. The particle size of the metal soap is such that it does not exceed the film thickness of the solid lubricating film. The binder resin contains a water-soluble or water-dispersible polymer and copolymer, and contains more than 90% by weight of the polymer and copolymer having an acrylate or methacrylate structure.
2. The solid lubricating film-forming agent according to claim 1, wherein As the additive, at least one of aqueous ammonia and a primary amine is further contained.
3. The solid lubricating film-forming agent according to claim 1 or claim 2, wherein The lower alcohol comprises one or more lower alcohols selected from methanol, ethanol, isopropanol, n-propanol and industrial ethanol, and the volume of the lower alcohol is 0.5 or more relative to the volume 100 of water in the solvent.
4. The solid lubricating film-forming agent according to any one of claims 1 to 3, wherein The metal soap and alkaline soap components constituting the solid lubricant include one or more soaps, wherein the soap is a compound formed of a fatty acid selected from the following Group A and a metal element selected from the following Group B, The weight of the metal soap is more than 95% of the total weight of the metal soap and the alkaline soap. Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid; Group B: Na, K, Mg, Ca, Zn.
5. The solid lubricating film-forming agent according to any one of claims 1 to 4, wherein The particle size of the metal soap is 10 μm or less.
6. The solid lubricating film-forming agent according to any one of claims 1 to 5, wherein The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of one or more monomers selected from the following (1) to (4), and the copolymer is a copolymer containing two or more monomers selected from the following (1) to (4). (1) Monomers mainly composed of acrylate, methacrylate and their derivatives; (2) monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters and their derivatives among acrylates, methacrylates and their derivatives; (3) a monomer grafted with (1) or (2); (4) A monomer of either or both of a vinyl compound and a urethane compound.
7. The solid lubricating film-forming agent according to any one of claims 1 to 6, wherein The reagent has a flash point exceeding 60°C or is flame retardant.
8. The solid lubricating film-forming agent according to any one of claims 1 to 7, wherein When the specific gravity of the solvent is set to 1 and the volume of the solvent is converted to weight, The weight of the solvent is 0.7 times or more and 100 times or less of the total weight of the solid lubricant and the binder resin, The weight of the solid lubricant is 0.1 times or more and 1.0 times or less the weight of the binder resin.
9. The solid lubricating film-forming agent according to any one of claims 1 to 8, wherein The viscosity of the reagent is 1000 mPa·s or less.
10. The solid lubricating film-forming agent according to any one of claims 1 to 9, wherein On the metal surface, 0.1g / mm 2 When the coating amount is applied in the following manner, the coating has an early drying property that allows the coating to dry within 30 minutes when left to dry in a windless atmosphere at normal temperature.
11. The solid lubricating film-forming agent according to any one of claims 1 to 10, wherein On the metal surface, 0.1g / mm 2 When the coating amount below is applied, it has an early drying property that allows drying within 5 minutes when drying is performed in an air environment at room temperature with air blowing at 1 m / sec or more.
12. A method for producing a reagent, which is a method for producing a solid lubricating film-forming reagent according to any one of claims 1 to 11, wherein: The metal soap is prepared by dispersing the metal soap in a lower alcohol to make it turbid and then adding the resulting dispersion into water as a solvent.
13. A method for applying a reagent, which is a method for applying the solid lubricating film-forming reagent according to any one of claims 1 to 11 onto the surface of a tubular member, wherein: The reagent is applied while the tubular member is subjected to axial rotation.
14. An oil country pipe having a lubricating film having a solid lubricating film formed on a threaded portion, wherein: In the solid lubricating film, a solid lubricant is dispersed in a binder resin. The solid lubricant contains a soap component including at least a metal soap of a metal soap and an alkaline soap component, wherein the metal soap component accounts for 95% or more of the total weight of the metal soap and the alkaline soap component. The particle size of the metal soap is such that it does not exceed the film thickness of the solid lubricating film. The binder resin contains a water-soluble or water-dispersible polymer and copolymer, and contains more than 90% by weight of the polymer and copolymer having an acrylate or methacrylate structure.
15. The oil well pipe according to claim 14, wherein: The metal soap and alkaline soap components constituting the solid lubricant include one or more soaps, wherein the soap is a compound formed of a fatty acid selected from the following Group A and a metal element selected from the following Group B, The weight of the metal soap is 95% or more of the total weight of the metal soap and the alkaline soap. Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid; Group B: Na, K, Mg, Ca, Zn.
16. The oil well pipe according to claim 14 or claim 15, wherein: The particle size of the metal soap is 10 μm or less.
17. The oil country pipe according to any one of claims 14 to 16, wherein: The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of one or more monomers selected from the following (1) to (4), and the copolymer is a copolymer containing two or more monomers selected from the following (1) to (4). (1) Monomers mainly composed of acrylate, methacrylate and their derivatives; (2) monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters and their derivatives among acrylates, methacrylates and their derivatives; (3) a monomer grafted with (1) or (2); (4) A monomer of either or both of a vinyl compound and a urethane compound.
18. The oil country pipe according to any one of claims 14 to 17, wherein: The solid lubricating film has a film thickness of 1 μm or more and 100 μm or less, and is soft with a hardness of H or less in pencil hardness.
19. An oil well pipe threaded joint, which is formed by connecting a sleeve with an internal thread and a pin with an external thread, wherein: At least one of the sleeve and the pin is constituted by the oil country pipe according to any one of claims 14 to 18 .
20. An oil well pipe threaded joint, which is formed by connecting a sleeve with an internal thread and a pin with an external thread, wherein: The oil country pipe of one of the sleeve and the pin is constituted by the oil country pipe according to any one of claims 14 to 18, A film having a higher hardness than the solid lubricating film is formed on the threaded portion of the other oil country tubular good.
Citation Information
Patent Citations
Screw joint for steel pipe
JP2002327874A
Threaded joints for steel pipes
JP2008537062A
Strut unit connection device adaptable to base-isolated structure
JP2009057754A
Screw joint for steel pipe
JP2016028211A
Recording head filing liquid, ink set and inspection metho of recording head
JP2022134375A